Lithium / sodium ion battery anode material

KR103022538B1Active Publication Date: 2026-09-18ECHION TECH LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020227016651
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-28
Filing Date
2020-10-08
Publication Date
2026-09-18
Estimated Expiration
2040-10-08

Smart Images

  • Figure 112022052423712-PCT00016_ABST
    Figure 112022052423712-PCT00016_ABST
Patent Text Reader

Abstract

The present invention relates to an active electrode material and a method for manufacturing the same. Such a material is useful as an active electrode material for lithium-ion or sodium-ion batteries. The present invention provides an active electrode material represented by the general formula [M1]x[M2](1-x)[Nb]y[O]z, wherein, in the general formula, M1 and M2 are different; M1 represents one or more of Ti, Mg, V, Cr, W, Zr, Mo, Cu, Fe, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Te, Se, Si, Sb, Y, La, Hf, Ta, Re, Zn, In, or Cd; M2 represents one or more of Mg, V, Cr, W, Zr, Mo, Cu, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Sb, Y, La, Hf, Ta, Zn, In, or Cd; x satisfies 0 < x < 0.5; y satisfies 0.5 ≤ y ≤ 49 and z satisfies 4 ≤ z ≤ 124.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an electrode active material and a method for manufacturing an electrode active material. Such a material is attracting attention as an electrode active material for, for example, lithium-ion or sodium-ion batteries. Background Technology

[0002] Lithium-ion (Li-ion) batteries are a commonly used type of rechargeable battery, with the global market estimated at $40 billion in 2018 and projected to grow to $200 billion by 2030. This massive market is segmented by diverse applications, ranging from transportation and utility-scale energy storage to consumer electronics and power tools. Consequently, intensive research and development is underway to improve the performance of rechargeable (secondary) lithium-ion batteries to meet the industrial demands of current technology [Goodenough and Park (2013)]. In particular, lithium-ion batteries are the technology of choice for electric vehicles, which have diverse requirements ranging from technical performance to environmental impact, providing a viable path for the eco-friendly automotive industry.

[0003] A typical lithium-ion battery consists of multiple cells connected in series or parallel. Each individual cell is generally composed of an anode (negative polarity electrode) and a cathode (positive polarity electrode), separated by a porous electrical insulating membrane (called a separator), and immersed in a liquid (called an electrolyte) that enables lithium-ion transport.

[0004] In most systems, the electrode consists of an electrochemically active material—which means it can chemically react with lithium ions to reversibly store and release them in a controlled manner—and, if necessary, is mixed with an electrically conductive additive (e.g., carbon) and a polymer binder. A slurry of these components is coated as a thin film onto a current collector (typically a thin foil of copper or aluminum) to form an electrode upon drying.

[0005] In known lithium-ion battery technology, the poor rate performance of graphite anodes during battery charging is a significant obstacle to applications in high-power electronics, automotive, and industrial sectors. Among the various potential alternatives recently proposed, Si, Si alloys, lithium titanate (LTO), and niobium oxide-based materials are major competitors to replace graphite as the active material of choice in high-power applications.

[0006] Battery charge rate is generally indicated by "C-rate". A 1C charge rate means a charging current that allows the battery to be fully charged in one hour, and a 10C charge means the battery can be fully charged in 1 / 10 of an hour (6 minutes).

[0007] Batteries relying on graphite anodes have fundamental limitations in terms of charging speed. Under nominal conditions, lithium ions are inserted into the anode active material during charging. As the charging speed increases, the typical graphite voltage profile poses a high risk of overpotential causing the anode potential to become < 0V relative to Li / Li+. This leads to a phenomenon known as lithium dendrite electroplating, where lithium metal is deposited on the surface of the graphite electrode instead of lithium ions. This results in the irreversible loss of active lithium, consequently causing rapid capacity degradation of the battery. In some cases, these dendrite deposits can grow large enough to penetrate the battery separator and cause a short circuit. This can trigger catastrophic battery failure leading to fire or explosion. Therefore, the fastest charging batteries with graphite anodes are limited to a charging speed of 5–7C, though often lower. Nevertheless, graphite anodes accounted for over 90% of the lithium-ion battery market in 2018.

[0008] Although Si and Si alloys have a high capacity, they have a short lifespan when charged and discharged at high speeds, and capacity retention is poor when increasing the rate from a low speed (e.g., 0.5C) to a higher speed (e.g., 5C). This is due to the non-uniform lithiation of active material particles during charging caused by the limited diffusion rate of lithium ions within the particles. The core of the active material particle (typically a 1-20 μm sphere) may not have enough time to be lithiated during rapid charging because lithium ions must diffuse from the particle surface; consequently, capacity retention is poor when the charging speed is increased. Furthermore, Si and Si alloy active materials physically expand by up to 400% in volume upon lithiation. Therefore, non-uniform particle lithiation induces internal mechanical stress within the particles, which can lead to particle decomposition and electrode fragmentation, resulting in poor electrode cycle life during rapid charging.

[0009] Lithium titanate (LTO) anodes do not undergo dendritic electroplating at high charge rates due to their high potential (1.6 V vs. Li / Li+) and do not experience volume expansion upon lithiation, resulting in excellent cycle life. For these two reasons, LTO batteries are generally considered high-safety batteries. However, LTO is a relatively poor electron and ion conductor, and capacity retention at high rates is limited unless the material is nanosized to increase surface area and carbon-coated to increase electron conductivity. This particle-level material engineering increases the cost of material particles and reduces the tapped density of the active LTO powder. This is significant because it results in low-density electrodes and a higher fraction of electrochemically inactive materials (e.g., binders, carbon additives).

[0010] The primary measure of anode performance is volumetric capacity (mAh / cm³), which is the amount of charge (i.e., lithium ions) that can be stored per unit volume of the anode. This is a critical factor in determining the total cell energy density on a volumetric basis (Wh / L). Volumetric capacity can be estimated as the product of electrode density, the specific capacity of the active material, and the ratio of the active material to the electrode. LTO anodes generally have a relatively low specific capacity (c. 170 mAh / g compared to c. 330 mAh / g for graphite), which, combined with the low electrode density (typically 1.9 g / cm³) and low active material fraction (<87%) described above, results in a very low volumetric capacity (<300 mAh / cm³), consequently leading to low cell energy density and a high $ / kWh cost. Consequently, despite their long cycle life, fast-charging capacity, and high safety, LTO batteries are generally limited to specific niche applications.

[0011] Mixed niobium oxides (MNO) were first identified as potential battery materials in the academic literature of the 1980s [Cava et al. (1983); Cava et al. (1984)], but they generated limited interest at the time because there were no commercially available cathodes that matched their rate performance.

[0012] Interest in MNO anodes was revived in the early 2010s as it was demonstrated that practical batteries combining TiNb2O7 anodes with commercially available LNMO cathodes exhibited promising performance in terms of rate performance, cycle life, and energy density [Goodenough and Park (2013)]. Selected MNO anodes, such as TiNb2O7, provide characteristics similar to LTO in terms of high operating potential (1.6 V) and low volume expansion (<5%) compared to Li / Li+, resulting in safe fast charging and long cycle life (>10,000 cycles). A major advantage of MNO anodes is that they can achieve significantly higher capacity than LTO (e.g., c. 300 mAh / g for TiNb2O7), which improves cell energy density. However, there are limitations similar to LTO, as electronic conductivity in MNO materials such as TiNb2O7 is generally too low to maintain fast charging rates without particle engineering and carbon coating.

[0013] On the other hand, other MNOs, such as Nb2O5, which are batteries studied in the 1980s and generally have a so-called "Wadsley-Roth" or "bronze" crystal structure, have an extremely fast lithium ion diffusion rate 10 -14 -10 -10 cm 2 s -1 (LTO is generally 10 -17 cm 2 s -1It was recently revealed that [Griffith et al. (2016)] can provide [Lim]. This can potentially improve electrode density (i.e., >2.5 g / cm³) and thus improve volumetric capacity (>600 mAh / cm³) and cell energy density. However, several issues, such as low electronic conductivity, lifetime problems due to "micromaterials" (crystals with a size of about 1–10 μm), and a "sloping" lithiation voltage profile, limit the commercial deployment of these materials. The lithiation voltage profile refers to the shape of the anode potential versus the amount of lithium inserted into the anode. LTO and TiNb2O7 have "flat" voltage profiles, whereas materials such as Nb2O5 generally have "sloping" voltage profiles. An overly sloping voltage profile creates a large voltage window, making overall cell balancing difficult in commercial batteries.

[0014] In particular, TiNb2O7 has additional limitations for applications in high-power battery technology. Other MNOs (e.g., Nb 12 MoO 33 = 4.0x10 -14 cm 2 s -1 Compared to )[Zhu 2019], the lithium ion diffusion rate (8.0x10 -16 cm 2 s -1 ) is limited, so performance at high power is limited. In particular, this limits the utilization of pseudocapacitive charge storage mechanisms, which are a major advantage of using MNOs for high power [Yang 2017].

[0015] US9515319B2 discusses TiNb2O7 and considers variations of this material but does not exemplify them. However, the feedstocks and methods used in this disclosure are expensive (furnace processing at 1500 °C for up to 50 hours), and the produced materials exhibit low initial Coulomb efficiencies (84.7%, 86.5%). US2015 / 0270543A1 and KR20150131800A disclose variations of TiNb2O7.

[0016] US2019 / 0288283A1 discloses a lithium niobium composite oxide, wherein as an essential feature, a portion of the niobium must be substituted with at least one element selected from Fe, Mg, Al, Cu, Mn, Co, Ni, Zn, Sn, Ti, Ta, V, and Mo.

[0017] The present invention was devised in light of the above considerations.

[0018] The inventors have realized that, despite the obvious problems presented by the prior art, it is possible to provide an active electrode material that overcomes some or all of the problems presented by the conventional materials discussed above.

[0019] Accordingly, in the first embodiment, the present invention is the general formula [M1] x [M2] (1-x) [Nb] y [O] z Provides an active electrode material represented by, where:

[0020] M1 and M2 are different;

[0021] M1 represents one or more of Ti, Mg, V, Cr, W, Zr, Mo, Cu, Fe, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Te, Se, Si, Sb, Y, La, Hf, Ta, Re, Zn, In, or Cd;

[0022] M2 represents one or more of Mg, V, Cr, W, Zr, Mo, Cu, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Sb, Y, La, Hf, Ta, Zn, In, or Cd; where

[0023] x satisfies 0 < x < 0.5;

[0024] y satisfies 0.5 ≤ y ≤ 49;.

[0025] z satisfies 4 ≤ z ≤ 124.

[0026] Materials in which M1 and M2 differ may also be referred to as mixed cationic active materials or complex oxide active materials. These terms are used interchangeably in this disclosure to refer to materials of the general formula as described above. Such materials are non-mixed cationic active materials (e.g., general formula [M] x [Nb] y [O] z It can provide improved electrochemical properties compared to a material having (where M represents a single ion).

[0027] In particular, as demonstrated by the examples, the inventors have discovered that replacing non-Nb cations to form a mixed cation structure can increase entropy in the crystal structure and reduce the potential energy barrier for Li-ion diffusion through the introduction of minor defects. The modification by creating a mixed cation structure that maintains the same overall oxidation state as the undeformed crystal structure demonstrates potential improvements by altering the ionic radius, which can induce minor changes in crystal parameters and lithium-ion cavities that can enhance electrochemical properties. For example, by replacing with cations of a larger ionic radius, the unit cell can be scaled compared to the undeformed structure, which can result in a higher Li-ion diffusion rate. The modification by creating a mixed cation structure that results in an increased oxidation state is compounded with the introduction of additional electron-holes into the structure to aid electrical conductivity, and similar potential benefits are exhibited due to the altered ionic radius. Modifications resulting from the creation of mixed cationic structures that lead to a reduced oxidation state are compounded with oxygen vacancies and the introduction of additional electrons into the structure to aid electrical conductivity, exhibiting similar potential benefits due to the altered ionic radius. Modifications caused by inducing oxygen deficiency during high-temperature processing under inert or reducing conditions provide reduced structures with significantly improved electrical conductivity. The combination of mixed cationic structures and induced oxygen deficiency allows for several beneficial effects.

[0028] As explained above, M1 represents one or more of Ti, Mg, V, Cr, W, Zr, Mo, Cu, Fe, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Te, Se, Si, Sb, Y, La, Hf, Ta, Re, Zn, In, or Cd. M2 represents one or more of Mg, V, Cr, W, Zr, Mo, Cu, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Sb, Y, La, Hf, Ta, Zn, In, or Cd. The phrase 'represents one or more of' is intended to mean that M1 or M2 may each represent two or more elements in their respective lists. An example of such a material is Ti 0.05 W 0.25 Mo 0.70 Nb 12 O 33 is. Here, M1 is Ti x' W x'' (Here, x' + x'' = x), and M2 represents Mo, x=0.3, y=12, z=33. Another example of such a material is Ti 0.05 Zr 0.05 W 0.25 Mo 0.65 Nb 12 O 33 is. Here, M1 is Ti x' Zr x'' W x''' (Here, x' + x'' + x''' = x), and M2 represents Mo, x=0.35, y=12, z=33.

[0029] Optionally, M1 represents one or more of K, Mg, Ca, Y, Ti, Zr, Hf, V, Ta, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, Si, Ge, Sn, and Sb. M1 represents one or more of Ti, Mg, V, Cr, W, Zr, Mo, Cu, Ga, Ge, K, Ni, Al, Hf, Ta, or Zn. Preferably, M1 represents one or more of Ti, Mg, V, Cr, W, Zr, Mo, Ga, Ge, Al, or Zn.

[0030] M2 does not represent Ti. In other words, preferably, Ti is not a major non-Nb cation in the active electrode material. If M1 represents Ti alone, preferably x is 0.05 or less. If M1 represents one or more cations including Ti, preferably the amount of Ti relative to the total amount of non-Nb cations is 0.05:1 or less.

[0031] Optionally, M2 is selected from one or more of Mo, W, V, Zr, Al, Zn, Ga, Ge, Ta, Cr, Cu, K, Mg, Ni, or Hf, and M2 may be selected from one or more of Mo, W, V, Zr, Al, Zn, Ga, or Ge. Preferably, M2 is selected from one or more of Mo, W, V, or Zr. The inventors have discovered that when M2 is selected from one of these elements, the active electrode material may have improved electrochemical properties. M2 may consist of a single element.

[0032] As x satisfies 0 < x < 0.5, M2 is the major non-Nb cation of the active electrode material. Preferably, x satisfies 0.01 ≤ x ≤ 0.4, and more preferably, x satisfies 0.05 ≤ x ≤ 0.25, for example, x can be about 0.05.

[0033] Precise values ​​of y and z within a defined range may be selected to provide a charge-balanced, or substantially charge-balanced, crystal structure. Additionally or alternatively, precise values ​​of y and z within a defined range may be selected to provide a thermodynamically stable, or thermodynamically metastable, crystal structure.

[0034] In some cases, z can be defined in the form z=(z'-z'α), where α is a non-integer value less than 1; for example, if α satisfies 0 ≤ α ≤ 0.05, α can be greater than 0, i.e., α can satisfy 0 < α ≤ 0.05. If α is greater than 0, the active electrode material is an oxygen-deficient material, meaning the material has oxygen vacancies. Such a material does not have precise charge balance but is considered "substantially charged" as indicated above. Alternatively, α can be equal to 0, in which case the material is not an oxygen-deficient material.

[0035] When α is 0.05, the number of oxygen vacancies corresponds to 5% of the total oxygen in the crystal structure. In some embodiments, α may be greater than 0.001 (0.1% oxygen vacancies), greater than 0.002 (0.2% oxygen vacancies), greater than 0.005 (0.5% oxygen vacancies), or greater than 0.01 (1% oxygen vacancies). In some embodiments, α may be less than 0.04 (4% oxygen vacancies), less than 0.03 (3% oxygen vacancies), less than 0.02 (2% oxygen vacancies), or less than 0.1 (1% oxygen vacancies). For example, α may satisfy 0.001 ≤ α ≤ 0.05. When the material is oxygen deficient, the electrochemical properties of the material may be improved. For example, resistance measurements may show improved conductivity compared to an equivalent non-oxygen-deficient material. As is understood, the percentage values ​​expressed here are represented as atomic percentages.

[0036] The oxygen deficiency of a substance (e.g., expressed as a percentage of oxygen deficiency) can be measured, for example, by thermogravimetric analysis (TGA) in an oxygen-rich atmosphere, by measuring how the sample mass changes over time due to the re-inclusion of oxygen into the oxygen deficiency. Alternatively, or additionally, oxygen deficiency can be qualitatively measured by evaluating the color of the substance against a non-oxygen-deficient sample of the same substance. For example, non-oxygen-deficient MoNb 12 O 33 It is white, grayish-white, or yellow. Oxygen-deficient MoNb 12 O <33 It has a purple tint. MoNb 12 O <33 When oxygen-deficient crystals are formed, a color change from white / grayish-white / yellow to purple may be observed.

[0037] M1 may have an oxidation state equal to or lower than that of M2. Preferably, M1 has an oxidation state lower than that of M2. When one or more elements are present as M1 and / or M2, the oxidation state will be understood to refer to M1 and / or M2 as a whole. For example, if 25 atomic percent of M1 is Ti and 75 atomic percent of M1 is W, the oxidation state of M1 is 0.25 × 4 (contribution of Ti) + 0.75 × 6 (contribution of W).

[0038] Advantageously, when M1 has a lower oxidation state than M2, this is compensated by the formation of oxygen vacancies, i.e., the formation of an oxygen-deficient active electrode material. The presence of oxygen vacancies is believed to improve the conductivity of the active electrode material and provide additional benefits, as demonstrated by the examples. Optionally, M1 contains at least one cation having a 4+ oxidation state and M2 contains at least one cation having a 6+ oxidation state. Optionally, M1 has a 4+ oxidation state and M2 has a 6+ oxidation state. M1 preferably has a different ionic radius from M2, most preferably a larger ionic radius. This changes the unit cell size and causes local distortion in the crystal structure. This is believed to improve electrochemical properties such as specific capacity and Coulomb efficiency by changing the cavity size and reducing the energy barrier for reversible lithiation, thereby altering the availability of Li-ion sites. The ionic radius is the Shannon ionic radius (RD Shannon, at the coordination and valence at which the ion is expected to adopt in the crystal structure of the active electrode material. Acta Cryst. , A32 It may be available in , 1976, 751-76).

[0039] The active electrode material may be a material selected from the group consisting of the following:

[0040] (i) M1 x Mo (1-x) Nb 12 O (33-33α)

[0041] M1 x W (1-x) Nb 12 O (33-33α)

[0042] M1 x V (1-x) Nb9O (25-25α)

[0043] M1 x Zr (1-x) Nb 24 O(62-62α)

[0044] M1 x W (1-x) No 0.57 O (4.43-4.43α)

[0045] M1 x W (1-x) No 0.89 O (5.22-5.22α)

[0046] M1 x Zn (1-x) No 17 O (43.5-43.5α)

[0047] M1 x Cu (1-x) No 17 O (43.5-43.5α)

[0048] M1 x Al (1-x) No 11 O (29-29α)

[0049] M1 x Ga (1-x) No 11 O (29-29α)

[0050] M1 x Ge (1-x) No 18 O (47-47α)

[0051] M1 x W (1-x) No -1.125 O (5.81-5.81α)

[0052] M1 x W (1-x) No -3.2 O (11-11α)

[0053] M1 x Al (1-x) No 49 O (124-124α)

[0054] M1 x Ga (1-x) No 49 O (124-124α) ; or

[0055] (ii) M1 x Mo(1-x) No 12 Oh (33-33α)

[0056] M1 x W (1-x) No 12 Oh (33-33α)

[0057] M1 x V (1-x) Nb9O (25-25α)

[0058] M1 x Zr (1-x) No 24 Oh (62-62α)

[0059] M1 x W (1-x) No 0.57 Oh (4.43-4.43α)

[0060] M1 x W (1-x) No 0.89 Oh (5.22-5.22α)

[0061] M1 x Zn (1-x) No 17 Oh (43.5-43.5α)

[0062] M1 x Al (1-x) No 11 Oh (29-29α)

[0063] M1 x Ge (1-x) No 18 Oh (47-47α) ; or preferably

[0064] (iii) M1 x In (1-x) No 12 Oh (33-33α)

[0065] M1 x W (1-x) No 12 Oh (33-33α)

[0066] M1 x V (1-x) Nb9O (25-25α)

[0067] M1 xZr (1-x) Nb 24 O (62-62α)

[0068] M1 x W (1-x) Nb 0.57 O (4.43-4.43α)

[0069] M1 x W (1-x) Nb 0.89 O (5.22-5.22α) ,

[0070] Here, M1 represents one or more of Ti, Mg, V, Cr, W, Zr, Mo, Cu, Fe, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Te, Se, Si, Sb, Y, La, Hf, Ta, Re, Zn, In, or Cd; x satisfies 0 < x < 0.5; and α satisfies 0 ≤ α ≤ 0.05.

[0071] In a particularly preferred embodiment, the active electrode material is M1 x Mo (1-x) Nb 12 O (33-33α) is. In another particularly preferred embodiment, the active electrode material is M1 x W (1-x) Nb 0.57 O (4.43-4.43α) is. In another particularly preferred embodiment, the active electrode material is M1 x Zn (1-x) Nb 17 O (43.5-43.5α) is. In another particularly preferred embodiment, the active electrode material is M1 x Al (1-x) Nb 11 O (29-29α) C. The examples show that these materials have characteristics that are particularly advantageous for use as active electrode materials.

[0072] In groups (i), (ii), and (iii) and particularly preferred embodiments, the material represents a specific unmixed cationic active material (i.e., x = 0) modified into a mixed cationic active material by substituting less than half of M2 with another element M1. Optionally, in such materials, M2 may also be substituted with Nb at non-Nb sites of the crystal structure. That is, M1 may represent one or more of Ti, Mg, V, Cr, W, Zr, Mo, Cu, Fe, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Te, Se, Si, Sb, Y, La, Hf, Ta, Re, Zn, In, Cd, or Nb. M1 may also represent the list of additional elements mentioned above and in the claims.

[0073] In a second aspect, the present invention is the general formula [M][Nb] y [O] z Provides an active electrode material represented by; the active electrode material is oxygen deficient; where M is composed of one of Mg, Cr, W, Mo, Cu, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Sb, Y, La, Hf, Ta, Zn, In, or Cd; y satisfies 0.5 ≤ y ≤ 49; and z satisfies 4 ≤ z ≤ 124.

[0074] The material according to the second aspect of the present invention is MoNb 12 O 33 , WNb 12 O 33 , W7Nb4O 31 , and W9Nb8O 47It is an oxygen-deficient analog of a known 'base' material such as. z can be defined as z=(z'-z'α), where α satisfies 0 < α ≤ 0.05. The description given above regarding the material according to the first embodiment specifying a possible range for α when defined as z=(z'-z'α) also applies to the material of the second embodiment of the present invention. For example, α can satisfy 0.001 ≤ α ≤ 0.05. The oxygen-deficient material according to the second embodiment has been found to have improved properties for use as an active electrode material compared to the stoichiometric 'base' material. For example, the material according to the second embodiment exhibits improved electrical conductivity.

[0075] M may be composed of one of Mo, W, Al, Zn, Ga, Ge, Ta, Cr, Cu, K, Mg, Ni, or Hf; or M may be composed of one of Mo, W, Al, Zn, Ga, or Ge; or preferably M may be composed of one of Mo, W, Al, or Zn.

[0076] The active electrode material of the second embodiment is the general formula [M] x [Nb] y [O] (z'-z'α) It is indicated by and can be selected from a group consisting of:

[0077] MoNb 12 O (33-33α)

[0078] WNb 12 O (33-33α)

[0079] W7Nb4O (31-31α)

[0080] W9Nb8O (47-47α)

[0081] Zn2Nb 34 O (87-87α)

[0082] Cu2Nb 34 O (87-87α)

[0083] AlNb 11 O (29-29α)

[0084] GaNb 11 O (29-29α)

[0085] GeNb 18 O (47-47α)

[0086] W 16 Nb -18 O (93-93α)

[0087] W5Nb 16 O (55-55α)

[0088] AlNb 49 O (124-124α)

[0089] GaNb 49 O (124-124α),

[0090] Here, α satisfies 0 < α ≤ 0.05.

[0091] These represent specific stoichiometric mixed niobium oxides modified into oxygen-deficient mixed niobium oxides.

[0092] The active electrode material of the second embodiment is the general formula [M] x [Nb] y [O] (z'-z'α) It is indicated by and can be selected from a group consisting of:

[0093] MoNb 12 O (33-33α)

[0094] WNb 12 O (33-33α)

[0095] W7Nb4O (31-31α)

[0096] W9Nb8O (47-47α)

[0097] Zn2Nb 34 O (87-87α)

[0098] AlNb 11 O (29-29α)

[0099] GeNb18 O (47-47α),

[0100] Here, α is 0 < α ≤ 0.05 is satisfied.

[0101] The active electrode material of the second embodiment is the general formula [M] x [Nb] y [O] (z'-z'α) It is indicated by and can be selected from a group consisting of:

[0102] MoNb 12 O (33-33α)

[0103] WNb 12 O (33-33α)

[0104] W7Nb4O (31-31α)

[0105] W9Nb8O (47-47α)

[0106] Here, α is 0 < α ≤ 0.05 is satisfied.

[0107] Optionally, M is W. That is, the active electrode material is the general formula [W][Nb] y [O] z It can be represented as. For example, the active electrode material is WNb 12 O (33-33α) , W7Nb4O (31-31α) , W9Nb8O (47-47α) , W 16 Nb -18 O (93-93α) , and W5Nb 16 O (55-55α) It can be selected from. Examples demonstrate that inducing oxygen deficiency in various different tungsten niobium oxides results in improved properties, for example, improved electrical conductivity compared to stoichiometric substrate oxides.

[0108] In a particularly preferred embodiment, the active electrode material is MoNb 12 O (33-33α) is. In another particularly preferred embodiment, the active electrode material is WNb 12 O(33-33α) is. In another particularly preferred embodiment, the active electrode material is W5Nb 16 O (55-55α) is. In another particularly preferred embodiment, the active electrode material is W7Nb4O (31-31α) is. In another particularly preferred embodiment, the active electrode material is Zn2Nb 34 O (87-87α) is. In another particularly preferred embodiment, the active electrode material is AlNb 11 O (29-29α) The examples show that these materials have characteristics that are particularly advantageous for use as active electrode materials.

[0109] The inventors incorporate a plurality of non-Nb cations to form a mixed cationic active material / complex oxide active material and / or (according to the first aspect of the invention), or create an oxygen deficiency (according to the second aspect of the invention) MoNb 12 O 33 , WNb 12 O 33 , ZrNb 24 O 62 , VNb9O 25, W7Nb4O 31 , and W9Nb8O 47 It was found that by modifying materials such as [material], it is possible to produce active electrode materials with improved electrochemical properties, particularly when used as anode materials.

[0110] The specific capacity / reversible delithiation capacity of the active electrode material according to the present invention may be 200 mAh / g or more, 225 mAh / g or more, 250 mAh / g or more, and up to about 300 mAh / g or more. Here, the specific capacity is defined as measured in the second cycle of a half-cell constant current cycling test at a rate of 0.05 C with a voltage window of 1.1-3.0 V for Li / Li+. It may be advantageous to provide a material having a high specific capacity, as this can provide improved performance in an electrochemical device containing the active electrode material.

[0111] In addition, the active electrode material according to the present invention may have an appropriate voltage profile measured in the second cycle of a half-cell constant current cycling test at a rate of 0.05C with a voltage window of 1.1-3.0V for Li / Li+. That is, the capacity of the material may be between 2.0V and 1.1V at lithiation >180mAh / g, and the capacity of the material may be between 1.1V and 2.0V at lithiation >180mAh / g.

[0112] When formulated or coated as an electrode (optional with a conductive carbon additive and a binder material), the bulk resistivity of the active electrode material according to the present invention may be 5 kΩ·cm or less, more preferably 2 kΩ·cm or less. Bulk resistivity can be a useful proxy measurement for the electronic conductivity of such a material. It may be advantageous to provide a material having a suitably low bulk resistivity, as this can provide improved performance in an electrochemical device comprising the active electrode material.

[0113] When measured in a lithium-ion half-coin cell using the described electrode, the DCIR and the generated area specific impedance (ASI) of the active electrode material may be 90 Ω or less (for DCIR) and 170 Ω·cm² or less (for ASI). It may be advantageous to provide a material having appropriately low DCIR and / or ASI, as this can provide improved performance in electrochemical devices containing the active electrode material. However, further improvements in DCIR / ASI values ​​may occur, for example, in the case of a carbon-coated active electrode material, or when the active electrode material is introduced into a commercial power cell with a cathode, or in an electrode manufactured by calendering and in a generally known manner. When measured in such an arrangement in a coin cell, the inventors have theorized that the ASI may be as low as, for example, 26 Ω·cm² or less.

[0114] The active electrode material according to the present invention is 10 -14 cm² s-1 It can have an excessive lithium diffusion rate. It may be advantageous to provide a material with an appropriately high lithium diffusion rate, as this can provide improved performance in electrochemical devices containing active electrode materials.

[0115] The active electrode material according to the present invention may have an electrode density of 2.5 g / cm³ or more after calendering. For example, an electrode density of up to 3.0 g / cm³ or more after calendering has been achieved. It may be advantageous to provide a material having such an electrode density because it can provide improved performance in an electrochemical device comprising the active electrode material. Specifically, when the electrode density is high, a high volumetric capacity can be achieved, such as weight capacity x electrode density x active material fraction = volumetric capacity.

[0116] The initial Coulomb efficiency of the active electrode material according to the present invention may be greater than 88%, more preferably greater than 90%. In some cases, the initial Coulomb efficiency of the active electrode material may be as high as 92% or more, 93% or more, or 94% or more. Since this can provide improved performance in an electrochemical device comprising the active electrode material, it may be advantageous to provide a material having a suitably high initial Coulomb efficiency. The initial Coulomb efficiency can be measured as the difference between the lithiation and delithiation capacities of the first charge / discharge cycle at C / 10 of the half-cell.

[0117] Additional optional features of the first and second embodiments of the present invention are described below.

[0118] The crystal structure of the active electrode material of the first embodiment, measured by X-ray diffraction, may correspond to the crystal structure of the unmodified form of the active electrode material, wherein the unmodified form is given by the formula [M2][Nb] y [O] z It is denoted as, where M2 consists of a single element, the undeformed form is not oxygen-deficient, and the undeformed form is selected from one or more of the following: M2 I Nb5O 13 , M2 I 6Nb 10.8 O 30 , M2 II Nb2O6, M2 II 2Nb 34 O 87 , M2 III Nb 11 O 29 , M2 III Nb 49 O 124 (M2 III 0.5 Nb 24.5 O 62 ), M2 IV Nb 24 O 62 , M2 IV Nb2O7, M2 IV 2Nb 10 O29 , M2 IV 2Nb 14 O 39 , M2 IV Nb 14 O 37 , M2 IV Nb6O 17 , M2 IV Nb 18 O 47 , M2 V Nb9O 25 , M2 V 4Nb 18 O 55 , M2 V 3Nb 17 O 50 , M2 VI Nb 12 O 33 , M2 VI 4Nb 26 O 77 , M2 VI 3Nb 14 O 44 , M2 VI 5Nb 16 O 55 , M2 VI 8Nb 18 O 69 , M2 VI Nb2O8, M2 VI 16 Nb 18 O 93 , M2 VI 20 Nb 22 O 115 , M2 VI 9Nb8O 47 , M2 VI 82 Nb 54 O 381 , M2 VI 31 Nb 20 O 143 , M2 VI 7Nb4O 31 , M2 VI 15 Nb2O 50 , M2 VI 3Nb2O 14 , 및 M2 VI 11 Nb 12O 63 Here, numbers I, II, III, IV, V, and VI represent the oxidation states of M2. This confirms that the undeformed form has been deformed without significantly affecting the crystal structure.

[0119] The crystal structure of the active electrode material of the second embodiment measured by X-ray diffraction may correspond to the crystal structure of the undeformed form of the active electrode material, where the undeformed form is the general formula [M][Nb] y [O] z It is indicated as, where the undeformed form is not oxygen-deficient, and where the undeformed form is M2 I Nb5O 13 , M2 I 6Nb 10.8 O 30 , M2 II Nb2O6, M2 II 2Nb 34 O 87 , M2 III Nb 11 O 29 , M2 III Nb 49 O 124 , M2 IV Nb 24 O 62 , M2 IV Nb2O7, M2 IV 2Nb 10 O 29 , M2 IV 2Nb 14 O 39 , M2 IV Nb 14 O 37 , M2 IV Nb6O 17 , M2 IV Nb 18 O 47 , M2 V Nb9O 25 , M2 V 4Nb 18 O 55 , M2 V 3Nb 17 O 50 , M2 VI Nb12 O 33 , M2 VI 4Nb 26 O 77 , M2 VI 3Nb 14 O 44 , M2 VI 5Nb 16 O 55 , M2 VI 8Nb 18 O 69 , M2 VI Nb2O8, M2 VI 16 Nb 18 O 93 , M2 VI 20 Nb 22 O 115 , M2 VI 9Nb8O 47 , M2 VI 82 Nb 54 O 381 , M2 VI 31 Nb 20 O 143 , M2 VI 7Nb4O 31 , M2 VI 15 Nb2O 50 , M2 VI 3Nb2O 14 , and M2 VI 11 Nb 12 O 63 Selected from, where numbers I, II, III, IV, V and VI represent the oxidation states of M. Thus, it can be confirmed that the undeformed form has been deformed without significantly affecting the crystal structure.

[0120] The crystal structure of the active electrode material determined by X-ray diffraction analysis may correspond to one or more of the following crystal structures:

[0121] (i) MoNb 12 O 33

[0122] WNb 12 O 33

[0123] VNb9O 25

[0124] ZrNb 24 YOU ARE 62

[0125] W7Nb4O 31

[0126] W9Nb8O 47

[0127] Zn2Nb 34 YOU ARE 87

[0128] Cu2Nb 34 YOU ARE 87

[0129] AlNb 11 YOU ARE 29

[0130] GaNb 11 YOU ARE 29

[0131] GeNb 18 YOU ARE 47

[0132] W 16 Nb 18 YOU ARE 93

[0133] W5Nb -16 YOU ARE 55

[0134] AlNb 49 YOU ARE 124

[0135] GaNb 49 YOU ARE 124 ; 또는

[0136] (ii) MoNb 12 YOU ARE 33

[0137] WNb 12 YOU ARE 33

[0138] VNb9O 25

[0139] ZrNb 24 YOU ARE 62

[0140] W4Nb7O 31

[0141] W9Nb8O 47

[0142] Zn2Nb 34 O 87

[0143] AlNb 11 O 29

[0144] GeNb 18 O 47 ; or preferably

[0145] (iii) MoNb 12 O 33

[0146] WNb 12 O 33

[0147] ZrNb 24 O 62

[0148] VNb9O 25

[0149] W7Nb4O 31

[0150] W9Nb8O 47 .

[0151] Here, the term 'corresponds' refers to peaks identified by X-ray diffraction analysis of the active electrode material corresponding to one or more reference crystal structures (e.g., MoNb 12 O 33, WNb 12 O 33, ZrNb 24 O 62, VNb9O 25, W7Nb4O 31 , and / or W9Nb8O 47It is intended to reflect that in the X-ray diffraction analysis of ), there may be a shift of 0.5 degrees or less from the corresponding peak (preferably 0.2 degrees or less, more preferably 0.1 degrees or less). Preferably, the crystal structure of the active electrode material does not correspond to the crystal structure of TiNb2O7, for example, preferably the measured XRD diffraction pattern of the active electrode material does not correspond to JCPDS Crystallography Database entry 00-039-1407 for TiNb2O7. Optionally, the crystal structure of the active electrode material is Ti2Nb 10 O 29 It does not correspond to the crystal structure of. Optionally, the crystal structure of the active electrode material is, M III Nb 11 O 29 , for example, FeNb 11 O 29 , GaNb 11 O 29 , CrNb 11 O 29 , and AlNb 11 O 29 It does not correspond to the crystal structure of.

[0152] At least a portion of the active electrode material may have a Wadsley-Roth crystal structure and / or a tetragonal tungsten bronze (TTB) crystal structure. Preferably, most of the active electrode material has a Wadsley-Roth crystal structure and / or a tetragonal tungsten bronze (TTB) crystal structure, and may have, for example, at least 50%, at least 60%, at least 70%, at least 80%, or at least 90% of the Wadsley-Roth crystal structure and / or tetragonal tungsten bronze (TTB) crystal structure based on volume. In a preferred embodiment, substantially all of the active electrode material may have a Wadsley-Roth crystal structure and / or a tetragonal tungsten bronze (TTB) crystal structure. When the material has such a crystal structure, it may have improved electrochemical properties.

[0153] The crystal formula of a charge-equilibrium and thermodynamically stable Wadsley-Roth crystal structure follows the following equation:

[0154] (1)

[0155] In this formula, O is oxygen (anion) and M (cation) is any combination of elements selected from Ti, Mg, V, Cr, W, Zr, Nb, Mo, Cu, Fe, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Te, Se, Si, Sb, Y, La, Hf, Ta, Re, Zn, In, or Cd. In the material according to the present invention, at least one of (M1, M2, M3…) comprises Nb.

[0156] Equation (1) is based on the crystal topology: m and n are the dimensions of the formed edge-shared superstructure blocks, ranging from 3 to 5 (integers). At the corners, the blocks are connected by an infinite ribbon (p=∞) only by edge-shared connections, by pairs (p=2) by partial edge-shared connections and partial tetrahedral connections, or by blocks isolated by tetrahedral connections only (p=1). When p is infinite, the equation is as follows:

[0157] (2)

[0158] Together, Equations (1) and (2) define a sample of the total composition for a Wadsley-Roth crystal structure. Preferably, the total crystal composition must also be charge-neutral and thermodynamically favorable.

[0159] More information can be found in the study of Griffith et al. (2017).

[0160] In the present disclosure, references to a tetragonal tungsten bronze (TTB) crystal structure (or simply a 'bronze' structure) refer to a tetragonal tungsten bronze (TTB) structure having partially filled tunnels. As described in the literature [Montemayor 1998], these steps consist of a framework of NbO6 octahedral covalent edges connected in such a way that 3-sided, 4-sided, and 5-sided tunnels are formed. A plurality of 5-sided tunnels are filled with W, Nb, O, or suitable metal cations to form the structure.

[0161] The active electrode material may further comprise Li and / or Na. In other words, the active electrode material may be a lithiated and / or sodiumated active electrode material. The active electrode material of the first embodiment is of the general formula [Li] λ [M1] x [M2] (1-x) [Nb] y [O] z or [Na] λ[M1] x [M2] (1-x) [Nb] y [O] z It can be represented as. The active substance of the second embodiment is the general formula [Li] λ [M][Nb] y [O] z or [Na] λ [M][Nb] y [O] z It can be represented as follows. x, y, and z satisfy the ranges discussed above, and λ is selected to provide a charge-balanced or substantially charge-balanced crystal structure, and / or a thermodynamically stable or thermodynamically metastable crystal structure.

[0162] The active electrode material may have a BET surface area in the range of 0.1–100 m² / g, or 0.5–50 m² / g, or 1–20 m² / g. Generally, a low BET surface area is desirable to minimize the reaction between the active electrode material and the electrolyte, e.g., BET. This includes a step of minimizing the formation of a solid electrolyte interface (SEI) layer during the first charge-discharge cycle of the electrode containing the material. However, a BET surface area that is too low results in unacceptably low charge rates and capacities due to the inaccessibility of most of the active electrode material to metal ions in the surrounding electrolyte. The term "BET surface area" refers to the surface area per unit mass calculated from measurements of the physical adsorption of gas molecules onto a solid surface using the Brunauer-Emmett-Teller theory. For example, the BET surface area can be determined according to ISO 9277:2010.

[0163] The active electrode material may comprise a plurality of primary crystallites (sometimes referred to as microcrystals or microcrystallites). The average diameter of the primary crystallites may be 10 nm to 10 μm, preferably 100 nm to 5 μm, but the most preferred diameter of the primary crystallites may vary depending on the intended application. For example, if the active electrode material is intended for use in ultra-high power products, a small primary crystallite size, e.g., 50 nm or less, or 30 nm or less, may be advantageous. If the active electrode material is intended for use in developing "high-energy power cells," a larger crystallite size, e.g., 5 μm or more, or 7 μm or more, may be advantageous.

[0164] Some or all of these primary grains may aggregate into secondary particles. Alternatively, the primary grains may not aggregate substantially. If some or all of these primary grains aggregate into secondary particles, the average diameter of the secondary particles (e.g., D when measured using solid-state powder laser diffraction) 50 The diameter is 1 μm to 30 μm, preferably 2 μm to 15 μm, but the most preferred diameter of the secondary particles may vary depending on the intended use. For example, if the active electrode material is intended for use in ultra-high power products, it may be advantageous for the secondary particle size to be small, e.g., 4 μm or less, 2 μm or less, or 1.5 μm or less. If the active electrode material is intended for use in developing "high-energy power cells," it may be advantageous for the secondary particle size to be larger, e.g., 8 μm or more, 12 μm or more, or 15 μm or more. The secondary particles may be porous.

[0165] The average diameter of primary grains and / or secondary particles can be measured using any conventional known technique, for example, by the steps of examining a sample of material using SEM imaging, selecting the number (n) of primary grains and / or secondary particles, and calculating the average diameter as the average diameter of the measured n primary grains / secondary particles, for example, where n is 30.

[0166] Another method for measuring secondary particle size is to use solid-state powder laser diffraction, for example, using a Horiba laser diffraction particle analyzer for dry powder with air pressure maintained at 0.3 MPa.

[0167] When the active electrode material is measured using solid-state powder laser diffraction, D 10 The secondary particle diameter may be at least 0.05 μm, or at least 0.1 μm, or at least 0.5 μm, or at least 1 μm. D 10 By maintaining the particle diameter within this range, the possibility of parasitic reactions in Li-ion batteries is reduced due to the reduced surface area, and processing with less binder in the electrode slurry becomes easier. n The term "diameter" refers to a diameter identified as n% or less based on the volume of a particle group.

[0168] When the active electrode material is measured using solid-state powder laser diffraction, D 90 The secondary particle diameter may be < 50 µm, < 20 µm, < 10 µm, or < 5 µm. D 90 By maintaining the particle diameter within this range, the proportion of large particle size distributions is minimized, making it easy to manufacture the material into a homogeneous electrode.

[0169] The active electrode material may include a carbon coating formed on the surface of primary crystal grains and / or secondary particles. Several suitable methods for forming a carbon coating on the surface of primary crystal grains and / or secondary particles are presented in the literature, e.g., Zhou (2012). Other suitable methods are described below. The carbon coating may be present in an amount of 5 w / w% or less based on the total weight of the active electrode material. The carbon coating may include graphite carbon.

[0170] When the active electrode has the form of a plurality of primary crystal grains and some or all of these primary crystal grains aggregate into porous secondary particles, the secondary particles may include at least a carbon coating formed on the pore surface of the secondary particles.

[0171] In a third aspect, the present invention provides an electrochemical device comprising an anode, a cathode, and an electrolyte disposed between the anode and the cathode, wherein the anode comprises an electrode active material according to the first or second aspect of the present invention.

[0172] The electrolyte can be a liquid electrolyte. Alternatively, or additionally, the electrolyte can be a solid-state electrolyte.

[0173] The anode may further comprise a conductive additive and / or binder. For example, the anode may have a composition of about 80 wt% active material, about 10 wt% conductive additive, and about 10 wt% binder. Alternatively, the anode may have a composition of about 91 wt% active material, about 5 wt% conductive additive, and about 4 wt% binder. The amount of active electrode material in the anode may be in the range of 70 wt% to 99 wt%, more preferably in the range of 75 wt% to 98 wt%, and even more preferably in the range of 85 wt% to 96 wt%.

[0174] In a fourth aspect, the present invention provides the use of an electrode active material according to the first or second aspect of the present invention as an anode active material, or as a component of an anode active material, together with a cathode and an electrolyte in (i) a lithium-ion battery for charging and discharging a lithium-ion battery; or (ii) a sodium-ion battery for charging and discharging a sodium-ion battery.

[0175] In a fifth aspect, the present invention provides a method for treating an electrode active material according to the first or second aspect of the present invention as or among an anode active material for the following: (i) a lithium-ion battery, wherein the method comprises the step of diffusing lithium ions into the anode active material; or (ii) a sodium-ion battery, wherein the method comprises the step of diffusing sodium ions into the anode active material.

[0176] In a sixth aspect, the present invention provides a method for manufacturing an active electrode material according to a first or second aspect of the present invention, said method,

[0177] A step of providing one or more precursor materials;

[0178] A step of mixing the above precursor materials to form a precursor material mixture; and

[0179] The method includes the step of forming an active electrode material by heat-treating the precursor material mixture in a temperature range of 400℃ to 1350℃.

[0180] In the case where it is preferable to prepare a material according to the first aspect of the present invention, preferably one or more precursor materials comprise an M1 ion source, an M2 ion source, and a source of Nb.

[0181] In the case where it is preferable to manufacture a material according to the second aspect of the present invention, preferably one or more precursor materials comprise an M source and an Nb source.

[0182] The phrase "M1 ion source" is used herein to describe a material containing M1 ions / atoms. The phrase "M2 ion source" is used herein to describe a material containing M2 ions / atoms. For example, the phrase "source of Mo / W / Zr / V / Nb" is used herein to describe a material containing Mo / W / Zr / V / Nb ions / atoms, where appropriate.

[0183] The precursor material may comprise one or more metal oxides, metal hydroxides, metal salts, or oxalates. For example, the precursor material may comprise one or more metal oxides of different oxidation states and / or different crystal structures. Examples of suitable metal oxide precursor materials are Nb2O5, NbO2, WO3, TiO2, and MoO2. 3, It includes, but is not limited to, V2O5, ZrO2, and MgO. However, the precursor material may not include metal oxides or may include ion sources other than oxides. For example, the precursor material may be a metal salt (e.g., NO3 - , SO3 - It may include ) or other compounds (e.g., oxalates). Preferably, one or more precursor materials include one or more of an Nb source, a Mo source, a W source, a Zr source, and / or a V source.

[0184] Some or all of the precursor material may be particulate material. If it is particulate material, it is preferably of diameter (e.g., D when measured using solid-state powder laser diffraction). 50It has an average particle size with a diameter of <20 μm. The average particle size may be, for example, 10 nm to 20 μm. Providing a particulate material having such an average particle size can help promote more intimate mixing of the precursor material, thereby leading to a more efficient solid-state reaction during the heat treatment step. However, since the particle size of one or more precursor materials can be mechanically reduced during the step of mixing the precursor materials to form a precursor material mixture, the precursor material does not need to have an initial particle size with a diameter of <20 μm.

[0185] The step of mixing / milling precursor materials to form a precursor material mixture may be performed by a method selected from dry or wet planetary ball milling, rolling ball milling, high-shear milling, air jet milling, and / or impact milling (though not limited thereto). The force used for mixing / milling may vary depending on the form of the precursor materials. For example, if some or all of the precursor materials have larger particle sizes (e.g., an average particle size with a diameter greater than 20 μm), the milling force may be selected to reduce the average particle size of the precursor materials, and the average particle size of the precursor material mixture is reduced to a diameter of 20 μm or less. When the average particle size of the particles in the precursor material mixture is 20 μm or less, the solid-state reaction of the precursor materials in the precursor material mixture can be promoted more efficiently during the heat treatment step.

[0186] The step of heat-treating the precursor material mixture can be performed for 1 hour to 24 hours, more preferably for 3 hours to 14 hours. For example, the heat treatment step can be performed for 1 hour or more, 2 hours or more, 3 hours or more, 6 hours or more, or 12 hours or more. The heat treatment step can be performed for 24 hours or less, 18 hours or less, 14 hours or less, or 12 hours or less.

[0187] In some methods, it may be advantageous to perform a two-step heat treatment. For example, a mixture of precursor materials may be heated at a first temperature for a first time and then heated at a second temperature for a second time. Preferably, the second temperature is higher than the first temperature. Performing this two-step heat treatment can help the solid-state reaction form a desired crystal structure.

[0188] The step of heat-treating the precursor material mixture can be performed in a gaseous atmosphere. The gaseous atmosphere may be an inert atmosphere or a reducing atmosphere. If it is desirable to produce an oxygen-deficient material, the step of heat-treating the precursor material mixture is preferably performed in an inert or reducing atmosphere. Suitable gaseous atmospheres include air, N2, Ar, He, CO2, CO, O2, H2, and mixtures thereof.

[0189] The present method may include one or more post-processing steps after the formation of the active electrode material.

[0190] In some cases, the present method may include a post-treatment step of heat-treating an active electrode material, which is sometimes referred to as 'annealing'. This post-treatment heat treatment step may be performed in a gas atmosphere different from the step of heat-treating a precursor material mixture to form an active electrode material. The post-treatment heat treatment step may be performed in an inert or reducing gas atmosphere. This post-treatment heat treatment step may be performed at a temperature of 500°C or higher, for example, about 900°C. Including the post-treatment heat treatment step creates, for example, a deficiency or defect in the active electrode material, for example, an oxygen deficiency. Advantageously, the post-treatment heat treatment step performed in an inert or reducing gas atmosphere can improve the electrical conductivity of the active electrode material. In this way, the active electrode material according to the second embodiment can be synthesized.

[0191] In some cases, the method may include a post-processing step of mixing the active electrode material with a carbon source to form a carbon coating on the active electrode material. Optionally, the mixture of the active electrode material and the carbon source may be heated to form a carbon coating on the active electrode material. Suitable carbon sources include, but are not limited to, carbohydrate materials (e.g., sugars, polymers); conductive carbon (e.g., carbon black); and / or aromatic carbon materials (e.g., pitch carbon).

[0192] One preferred method for forming a carbon coating includes the step of milling an active electrode material together with a carbon source, and then pyrolyzing the active electrode material and the carbon source under an inert or reducing atmosphere (e.g., in a furnace).

[0193] Another preferred method for forming a carbon coating involves mixing an active electrode material with a carbon source, dispersing the active electrode material and the carbon source in an aqueous slurry, and then spray drying. The resulting powder may optionally be pyrolyzed. If the carbon source is, for example, conductive carbon black, there is no need to pyrolyze the material after spray drying.

[0194] In some cases, the method may include a post-processing step of milling the active electrode material to change the particle size of the active electrode material. For example, the active electrode material may be processed by one or more processes including air jet milling, impact milling, high-shear milling, sieving, or ball milling. This may provide a more suitable particle size for use in the desired application of the active electrode material.

[0195] In a further embodiment, the present invention provides a use of dopant M1 to improve the properties of a base material for use as an active material for a metal-ion battery anode, wherein the base material has the structure M2Nb y O zIt has, and the dopant is a deformable material [M1] x [M2] (1-x) [Nb] y [O] z It is used to provide, wherein the modified material has improved properties compared to the base material. The improved properties may include improved initial Coulomb efficiency (exemplified by the difference in lithiation and delithiation capacity in the first charge / discharge cycle at C / 10 of the half-cell). The improved properties may include improved capacity retention when comparing high charge / discharge rates with lower rates (exemplified by 5C or 10C versus 0.5C). The improved properties may include improved specific capacity at low charge / discharge rates (exemplified by 0.1C in this specification). M1, M2, x, y, and z are as defined in this specification.

[0196] The present invention includes combinations of the embodiments and features and preferred features described above, except where such combinations are explicitly unacceptable or explicitly avoided. Brief explanation of the drawing

[0197] Embodiments and experiments illustrating the principles of the present invention will now be discussed with reference to the accompanying drawings: Fig. 1 Figure 1 shows the XRD diffraction patterns of samples 1, 4, 14, 2, 5, 15, 16, 18, and 22. Fig. 2 represents the XRD diffraction patterns of samples 8 and 9. Fig. 3 Figure 1 shows the XRD diffraction patterns of samples 6, 7, 17, 19, and 20. Fig. 4 represents the XRD diffraction patterns of samples 10, 11, and 21. Fig. 5 represents the XRD diffraction patterns of samples 12 and 13. Fig. 6 represents the TGA characterization of sample 3 in air. Fig. 7 represents the particle size distribution of samples 1, 2, 15, and 16. Fig. 8 represents the particle size distribution of sample 3. Fig. 9This is an SEM image of sample 3 before pyrolysis, and it is coated with conductive Au for imaging. Fig. 10 This is an SEM image of Sample 3 after pyrolysis (no conductive coating). Fig. 11 is the SEM image of samples 1 and 2; Fig. 12 Figure 1 shows representative lithiation and delithiation voltage profiles obtained by constant current cycling in the first two cycles with a half-cell configuration at a rate of 0.05 C for samples 1 and 16, a voltage window of 1.1–3.0 V. Fig. 13 Figure 1 shows representative lithiation and delithiation voltage profiles obtained by constant current cycling in the first two cycles for samples 6 and 7 with a half-cell configuration at a rate of 0.05C, a voltage window of 1.1–3.0 V; Fig. 14 Figure 1 represents the lithiation and delithiation capacities obtained with constant current cycling in a 1.1–3.0 V voltage window for half-cell configurations at current densities of 0.5 C, 1 C, 2 C, and 5 C (indicated by stepwise changes in data) for samples 1, 4, and 16; Fig. 15 represents the lithiation capacity obtained by constant current cycling in a 1.1–3.0 V voltage window for half-cell configurations at current densities of 0.5 C, 1 C, 2 C, 5 C, and 0.5 C (indicated by stepwise changes in data) for samples 6, 7, and 17; Fig. 16 (a) and (b) show the EIS measurements of samples 1, 7, and 16 at different axis scales; Fig. 17 Figure 1 shows the particle size distribution of Sample 16 before and after post-processing; Fig. 18 This is an SEM image of the electrode surface of Sample 22 focused on the surface of the active material particles; Fig. 19 Figure 1 shows representative lithiation and delithiation voltage profiles obtained by constant current cycling in the first two cycles for samples 12 and 13 with a half-cell configuration at a rate of 0.05C, a voltage window of 1.1–3.0 V; Fig. 20 This shows the XRD diffraction patterns of samples E1 and E2. Fig. 21Figure 1 shows the XRD diffraction patterns of samples E3, E4, and E5. Fig. 22 represents the XRD diffraction patterns of samples E6, E7, and E8. Fig. 23 This shows the XRD diffraction patterns of samples E9 and E10. Fig. 24 represents the particle size distribution of samples E2, E4, E7, and E10. Fig. 25 Figure 1 shows representative lithiation and delithiation voltage profiles obtained for samples E1 and E2 with a half-cell configuration at a rate of 0.1C, a voltage window of 1.1–3.0V, and constant current cycling in the first two cycles. Fig. 26 Figure 1 shows representative lithiation and delithiation voltage profiles obtained for samples E3 and E5 with a half-cell configuration at a rate of 0.1C, a voltage window of 1.1–3.0V, and constant current cycling in the first two cycles. Fig. 27 Figure 1 shows representative lithiation and delithiation voltage profiles obtained for samples E6 and E7 with a half-cell configuration at a rate of 0.1C, a voltage window of 1.1–3.0V, and constant current cycling in the first two cycles. Fig. 28 Figure 1 shows representative lithiation and delithiation voltage profiles obtained for samples E9 and E10 with a half-cell configuration at a rate of 0.1C, a voltage window of 1.1–3.0V, and constant current cycling during the first two cycles. The x-axis is based on the State of Charge (SOC), allowing the curve to be normalized to the maximum capacity and the shape of the curve to be evaluated. Fig. 29 This shows the XRD diffraction pattern of E11-E14. Specific details for implementing the invention

[0198] Aspects and embodiments of the present invention will now be discussed with reference to the accompanying drawings. Further aspects and embodiments will be apparent to those skilled in the art. All documents mentioned in this text are incorporated herein by reference.

[0199] As summarized in Table 1 below, a number of different materials were prepared and characterized. Generally, these samples can be divided into several groups.

[0200] Samples 1, 2, 3, 4, 5, 14, 15, 16, 18, and 22 are MoNb 12 O 33 (M 6+ Nb 12 O 33 , belongs to the same family on Wadsley-Roth based on a 3x4 octahedral block with tetrahedrons at each block corner. The block includes edge sharing between NbO6 octahedrons, M 6+ They are interconnected by edge sharing between O4 tetrahedra and NbO6 octahedra. Sample 1 has a mixed crystal configuration (equilibrium WNb) in Samples 2 through 4 and / or Samples 14, 15, 16, 18, and 22. 12 O 33 It is a basic crystal structure modified into a mixed metal cation structure by exchanging one or more cations in the mixture. Oxygen deficiency is generated in the basic crystal of Sample 5 and the mixed metal cation structure 18. Sample 3 is a spray-dried and carbon-coated version of the crystal formed in Sample 2, and Sample 22 is a spray-dried and carbon-coated version of the crystal formed in Sample 16.

[0201] Samples 6, 7, 17, 19, and 20 are ZrNb 24 O 62 (M 4+ Nb 24 O 62 It belongs to the same family on Wadsley-Roth based on an octahedron of 3x4 blocks with half of a tetrahedron at each corner of the block.

[0202] Samples 8, 9, and E11 are WNb 12 O 33 (M 6+ Nb 12 O 33It belongs to the same family on Wadsley-Roth based on a 3x4 NbO6 octahedral block with a tetrahedron at each block corner.

[0203] Samples 10, 11, and 21 are VNb9O 25 (M 5+ Nb9O 25 It belongs to the same family on Wadsley-Roth based on a 3x3 NbO68-sided block with tetrahedrons at each block edge.

[0204] Samples 12, 13, and E14 are W7Nb4O 31 (M 6+ 7Nb4O 31 It belongs to the same TTB (tungsten tetragonal bronze) family based on ). This is a tetragonal tungsten bronze structure in which MO6 (M = 0.4 Nb + 0.6 W) octahedrons exclusively share corners with 3, 4, and 5-sided tunnels. Some of these tunnels are filled with -OMO- chains, while others are open for lithium ion transport and storage.

[0205] Samples E1, E2, and E13 are Zn2Nb 34 O 87 (M 2+ 2Nb 34 O 87 It belongs to the same family of Wadsley-Roth phases based on ). This orthorhombic phase is an MO6 octahedron (M=Zn +2 / Nb +5 It consists of 3x4 blocks, and the blocks are entirely connected by shared edges and there are no tetrahedrons.

[0206] Samples E3, E4, E5, and E12 are AlNb 11 O 29 (M 3+ Nb 11 O 29It belongs to the same family on the Wadsley-Roth based on ). The structure belongs to a monoclinic shear structure in which 3x4 octahedral blocks are connected entirely through edge sharing, and there are no tetrahedrons.

[0207] Samples E6, E7, and E8 are GeNb 18 O 47 (M 4+ Nb 18 O 47 It belongs to the same family on the Wadsley-Roth plane based on ). The structure is similar to Sample 10, which has a 3x3 NbO6 octahedral block and a single tetrahedral block connecting the blocks at the edges. However, the structure is V 5+ Instead Ge +4 Includes inherent defects caused by

[0208] Samples E9 and E10 are W5Nb 16 O 55 (M 6+ 5Nb 16 O 55 It belongs to the same family on the Wadsley-Roth plane based on ). The structure consists of 4x5 blocks connected at the sides by edge-sharing (W,Nb)O6 and at the edges by WO4 tetrahedrons. This structure is similar to samples 8 and 9, but the block size is larger.

[0209]

[0210]

[0211] Table 1 - Summary of various synthesized compositions. Samples marked with * are comparison samples.

[0212] Material synthesis

[0213] The samples listed in Table 1 were synthesized using a solid-state route. In the first step, commercial metal oxide precursor powders (Nb2O5, NbO2, MoO3, ZrO2, TiO2, WO3, V2O5, ZrO2, K2O, CoO, Fe2O3, GeO2, Ga2O3, Al2O3, ZnO and / or MgO) were mixed in stoichiometric ratios and planetary ball milled at 550 rpm for 3 hours in a milling medium with a zirconia bottle and ball-to-powder ratio of 10:1. The resulting powder was then heated in a static muffle furnace in air to form the desired crystalline phase. Samples 1 to 5 and 12 to 16, 18, and 22 were heat-treated at 900°C for 12 hours; Samples 6 to 9, 17, 19, and 20 were heat-treated at 1200°C for 12 hours, and samples 6, 7, 17, 19, and 20 underwent an additional heat-treatment step at 1350°C for an additional 4 hours; samples 10, 11, and 21 were heat-treated at 1000°C for 12 hours. Samples 3 and 22 were further mixed with a carbohydrate precursor (e.g., sucrose, maltodextrin, or other water-soluble carbohydrates), dispersed in an aqueous slurry with an ionic surfactant at concentrations of 5, 10, 15, or 20 w / w%, and spray-dried in a laboratory-scale spray dryer (inlet temperature 220°C, outlet temperature 95°C, sample introduction rate 500 mL / h). The resulting powder was pyrolyzed in nitrogen at 600°C for 5 hours. Samples 5 and 18 were further annealed in nitrogen at 900°C for 4 hours.

[0214] Samples E1, E2, E6, E7, E8, E9, and E10 were ball-milled as described above and, if necessary, impingement milled at 20,000 rpm to obtain a particle size distribution of D90 < 20 μm, after which they were heat-treated in a muffle furnace at 1200°C in air for 12 hours; samples E8, E10, E11, E12, and E13 were additionally annealed in nitrogen at 1000°C for 4 hours; E14 was annealed in nitrogen at 900°C for 5 hours; and samples E3, E4, and E5 were heat-treated at 1300°C for 12 hours. After synthesis, samples E1 to E10 were deagglomerated to a desired particle size range by impingement milling or jet milling.

[0215] Elemental analysis of the sample

[0216] Elemental analysis was performed using ICP-MS / OES (Inductively-Coupled Plasma-Optical Emission Spectroscopy). Measurements were performed on a Thermo Scientific ICP-OES Duo iCAP 7000 series. Samples were decomposed using 5 ml of nitric acid and 1 ml of HF acid, and any instrumental changes were eliminated using internal standards. In this process, plasma is used to vaporize the material into atomic / ionic states of elements. The atoms are in an excited state due to high temperatures and decay to a steady state through energy transitions. The characteristic radiation emitted from each excited ion is measured and analyzed. The results are presented in Table 2 below.

[0217]

[0218] Table 2: Summary of ICP-OES elemental analysis results for samples 1, 2, 4, 14, 3, 16, 9, 11, and 17.

[0219] This elemental analysis table demonstrates that substantially expected cation ratios were achieved for each tested composition.

[0220] XRD characterization of the sample

[0221] The phase purity of some samples was analyzed using a Rigaku Miniflex powder X-ray diffractometer in the 2θ range (10-70°) at a scan rate of 1° / min.

[0222] Figure 1 shows the XRD diffraction patterns measured for samples 1, 4, 14, 2, 5, 15, 16, 18, and 22 associated with Comparative Study A. All diffraction patterns are at the same location (within the instrument error, i.e., 0.1°) and MoNb 12 O 33 It corresponds to the JCPDS crystallography database entry JCPDS 73-1322. There is no amorphous background noise, and the peaks are sharp and intense. This indicates that all samples are in a pure phase and are crystalline, with a grain size of ~200 nm according to the Scherrer equation, and a crystal structure of MoNb 12 O 33 It means that it matches.

[0223] Figure 2 shows the XRD diffraction patterns measured for samples 8 and 9. Figure 29 shows the XRD pattern for sample E11. All diffraction patterns have peaks at the same location (within the instrument error, i.e., 0.1°) and WNb 12 O 33 It corresponds to the JCPDS crystallography database entry JCPDS 73-1322. There is no amorphous background noise, and the peaks are sharp and intense. This indicates that all samples are in a pure phase and are crystalline, with a grain size of ~200 nm according to the Scherrer equation and a crystal structure of WNb 12 O 33 It means that it matches.

[0224] Figure 3 shows the XRD diffraction patterns measured for samples 6, 7, 17, 19, and 20 associated with Comparative Study B. All diffraction patterns have a peak at the same location (within the instrument error, i.e., 0.1°), and ZrNb 24 O 62It matches the corresponding JCPDS crystallography database entry JCPDS 01-072-1655. There is no amorphous background noise, and the peaks are sharp and intense. This indicates that all samples are in a pure phase and are crystalline, with a grain size of ~200 nm according to the Scherrer equation and a crystal structure of ZrNb 24 O 62 It means that it matches.

[0225] Figure 4 shows the XRD diffraction patterns measured for samples 10, 11, and 21. All diffraction patterns have a peak at the same position (within the instrument error, i.e., 0.1°), and VNb9O 25 It matches the corresponding JCPDS crystallography database entry JCPDS 00-049-0289. There is no amorphous background noise, and the peaks are sharp and intense. This indicates that all samples are in a pure phase and are crystalline, with a grain size of ~200 nm according to the Scherrer equation and a crystal structure of VNb9O. 25 It means that it matches.

[0226] Figure 5 shows the measured XRD diffraction patterns for samples 12 and 13. Figure 29 shows the XRD pattern for sample E14. All diffraction patterns have peaks at the same position (within the instrument error, i.e., 0.1°), and W7Nb4O 31 It matches the corresponding JCPDS crystallography database entry JCPDS 00-020-1320. There is no amorphous background noise, and the peaks are sharp and intense. This indicates that all samples are in a pure phase and are crystalline, with a grain size of ~200 nm according to the Scherrer equation and a crystal structure of W7Nb4O. 31 It means that it matches.

[0227] Figure 20 shows the XRD diffraction patterns measured for samples E1 and E2. Figure 29 shows the XRD pattern for sample E13. All diffraction patterns have peaks at the same position (within 0.1–0.2°) and are consistent with JCPDS crystallography database entry JCPDS 22-353. There is no amorphous background noise, and the peaks are sharp and intense. This indicates that all samples are in a pure phase and are crystalline, with a grain size of 52 ± 12 nm according to the Scherrer equation and a crystal structure of Zn2Nb 34 O 87 It means that it matches.

[0228] Figure 21 shows the XRD diffraction patterns measured for samples E3, E4, and E5. Figure 29 shows the XRD pattern for sample E12. All diffraction patterns have peaks at the same position (within 0.1–0.2°) and JCPDS crystallography database entry JCPDS 72-159 (isostructural Ti2Nb 10 O 29 It is consistent with ). There is no amorphous background noise, and the peaks are sharp and intense. This indicates that all samples are in a pure phase and are crystalline, with a grain size of 53 ± 16 nm according to the Scherrer equation and a crystal structure of AlNb 11 O 29 It means that it matches.

[0229] Figure 22 shows the XRD diffraction patterns measured for samples E6, E7, and E8. All diffraction patterns have peaks at the same position (within 0.1–0.2°) and ICSD Crystallography Database entry 72683 (equistructure PNb9O 25 It is consistent with ). There is no amorphous background noise, and the peaks are sharp and intense. This indicates that all samples are in a pure phase and are crystalline, with a grain size of 53 ± 3 nm according to the Scherrer equation and a crystal structure of GeNb 18 O 47 It means that it matches.

[0230] Figure 23 shows the XRD diffraction patterns measured for samples E9 and E10. All diffraction patterns have peaks at the same position (within 0.1–0.2°) and are consistent with JCPDS crystallography database entry JCPDS 44-0467. There is no amorphous background noise, and the peaks are sharp and intense. This indicates that all samples are in a pure phase and are crystalline, with a grain size of 37 ± 11 nm according to the Scherrer equation and a crystal structure of W5Nb 16 O 55 It means that it matches.

[0231] TGA characterization of the sample

[0232] Thermogravimetric analysis (TGA) was performed on some samples using a Perkin Elmer Pyris 1 system in a synthetic air atmosphere. The samples were first held at 30°C for 15 minutes, then heated from 30°C to 950°C at a rate of 5°C / min, and finally held at 950°C for 30 minutes. TGA was performed on sample 3 to quantify carbon content, and TGA was performed on sample 5 to show mass increase as oxygen vacancies were filled.

[0233] Figure 6 shows the TGA characteristics of Sample 3 in air. The sharp mass drop between ~400°C and 500°C is attributed to the decomposition of the carbon coating. The decomposition temperature corresponds to a mixture of amorphous carbon and graphite carbon. The amount of mass loss indicates that Sample 3 contains 1.1 w.% of carbon coating, which is consistent with the amount expected from the stoichiometry of the precursor.

[0234] Qualitative assessment of oxygen deficiency

[0235] As discussed above, samples 5 and 18 were heat-treated at 900°C for 12 hours to form an active electrode material, and then further annealed at 900°C in nitrogen (reducing atmosphere) during the post-treatment heat treatment step. After heat treatment in nitrogen, a color change from white to dark purple was observed, which indicates a change in the oxidation state and band structure of the material as a result of oxygen deficiency in the samples.

[0236] Samples E8, E10, E11, E12, and E13 were additionally annealed in nitrogen at 1000°C for 4 hours, and sample E14 was annealed in nitrogen at 900°C for 5 hours. Sample E7 changes from white to dark yellow when oxygen deficiency induced in sample E8 is introduced; sample E9 changes from grayish-white to bluish-gray when oxygen deficiency induced in sample E10 is introduced; sample 8 changes from grayish-white to light blue in E11; sample E3 changes from white to gray / black in E12; sample E1 changes from white to gray / black in E3; and sample 12 changes from light yellow to dark blue in E14.

[0237] Analysis of particle size distribution of the sample

[0238] The particle size distribution of the dry powder was obtained using a Horiba laser diffraction particle analyzer. The air pressure was maintained at 0.3 MPa. The results are presented in Table 3 below.

[0239]

[0240]

[0241] Table 3: Summary of particle size distribution statistics for samples 1, 2, 15, 16, 18, 3 before pyrolysis, 3 after pyrolysis, samples 16 and 18 after post-treatment, and samples E1-E14.

[0242] Figure 7 shows the particle size distribution for samples 1, 2, 15, and 16 (measured particle sizes are secondary particle sizes, not crystal or grain sizes), as a representative example of the particle size distribution obtained by the solid-state route without additional processing or size optimization in this study. The particle size distribution is generally dual-mode, with the first mode being ~10 μm and the second mode being ~90 μm. Sample 3 exhibits a significant difference in the particle size distribution pattern as shown in Figure 8 due to the spray drying and pyrolysis post-treatment steps.

[0243] All particle size distributions may also be refined through additional processing steps, such as spray drying, ball milling, high-shear milling, jet milling, or impact milling, to reduce the particle size distribution to a desired range (e.g., d90 < 20 μm, < 10 μm, or < 5 μm), as shown in Fig. 17 and Table 3. Generally, the particle size distribution is tuned by optimizing the phase formation process (i.e., solid-state synthesis route) and post-processing steps for the target application. For example, for high-power Li-ion electrodes, a lower average particle size is generally targeted among other considerations.

[0244] Figure 24 shows the particle size distribution for samples E2, E4, E7, and E10 in their final forms, which are processed into electrode slurry and ink.

[0245] SEM characterization of the sample

[0246] The morphology of some samples was analyzed using a scanning electron microscope (SEM).

[0247] Figures 9 and 10 show SEM images of Sample 3 before and after pyrolysis. Carbon-coated porous microsphere morphology is observed, and the primary crystal grains are organized into secondary particles. It can be seen that the material possesses homogeneous porous particles capable of efficient packing to form high-density electrodes. Since there is no need to apply a conductive coating to perform SEM imaging, conductivity is qualitatively significantly improved, implying that the surface conductivity of the material has improved by approximately tenfold. Figure 18 is an SEM image of the particle surface on the electrode of Sample 22, and the conductive carbon black particles contained in the electrode can also be seen on the right side of the image. This visually demonstrates evidence of an conformal carbon coating around the MNO material.

[0248] Figure 11 shows SEM images of samples 1 and 2, provides XRD and PSD data, and shows dense secondary micron-sized particles composed of ~200 nm primary crystal grains.

[0249] Electrochemical testing of the sample

[0250] Electrochemical tests were performed in a half-coin cell (CR2032 size) for initial analysis. In half-coin tests, the material is tested against a Li metal electrode to evaluate basic performance. In the following examples, the active material composition to be tested (although it is also possible to form an aqueous slurry using water instead of NMP) was mixed with N-methylpyrrolidone (NMP), carbon black acting as a conductive additive, and a poly(vinyl difluoride (PVDF) binder, and a slurry was formed by mixing using a laboratory-scale centrifugal planetary mixer. The non-NMP composition of the slurry was 80 w.% active material, 10 w.% conductive additive, and 10 w.% binder. Then, the slurry was coated onto an Al foil current collector with a desired loading of 1 mg / cm² by doctor blade coating and dried in a vacuum oven for 12 hours. The electrode was punched to the desired size and placed inside a steel coin cell casing with a separator ( Celgard The porous PP / PE, Li metal, and electrolyte (1M LiPF6 in EC / DEC) were combined and sealed under pressure. Then, formation cycling was performed at a low current rate (C / 20) for two full charge and discharge cycles. After formation, additional cycling at a fixed or variable current density may be performed as needed. This test is referred to as "half-cell galvanostatic cycling" for future reference. For samples E1-E10, the electrolyte was changed from 3:7 EC / DEC to 1.3M LiPF6, and formation cycling was performed at C / 10 for two charge / discharge cycles within a limit of 1.1 to 3.0 V. The values ​​shown for this sample are the average of three measurements, and the error is the standard deviation.

[0251] A uniform, smooth, and defect-free coating on the current collector foil was also prepared as described above using a centrifugal planetary mixer with a composition of 94 w.% active material, 4 w.% conductive additive, and 2 w.% binder. To demonstrate a possible volumetric capacity of > 700 mAh / cm³ in a voltage range of 0.7 to 3.0 V at C / 20, and > 640 mAh / cm³ in a voltage range of 1.1 to 3.0 V at C / 5, the coating was calendered at 80°C at a load of 1.3 - 1.7 mAh / cm² with a density of up to 3.0 g / cm³. This is an important demonstration that these materials are viable in commercially concentrated electrode power cell formulations that allow for high volumetric capacity while maintaining performance after calendering at high electrode densities. Loads of up to 1.0, 1.5, 2.0, 2.5, or 3.0 mAh / cm² may be useful for lithium-ion batteries focused on power performance; loads greater than 3.0, 4.0, or 5.0 mAh / cm² are useful for the energy-intensive performance of lithium-ion batteries. The calendering of these materials has been demonstrated down to electrode porosity values ​​of 35%, typically in the range of 35-40%; defined as the measured electrode density divided by the average of the actual densities of each electrode component adjusted to w / w%.

[0252] The electrical conductivity of electrodes made from the samples listed in Table 1 was measured using a 4-point probe thin-film resistivity meter. The slurry was formulated according to the procedure described above and coated onto a dielectric Mylar film with a load of 1 mg / cm². Then, the resistance of the coated film and a disk of the punched electrode size was measured using a 4-point probe. Bulk resistivity can be calculated from the measured resistance using the following equation.

[0253] (3) Bulk resistivity (ρ) = 2πs(V / I); R = V / I; s = 0.1cm

[0254] = 2πx0.1xR (Ω)

[0255] The results of this test are shown in Table 4 below.

[0256]

[0257] Table 4 - Summary of 4-point probe resistivity measurement results for samples 1, 2, 4, 5, 6, 7, 13 through 20, and 22

[0258] Four-point probe resistance was measured on samples E1-E14 to quantify electrical resistance. This was performed on a different Ossila instrument (T2001A3-UK) at 23°C for coating on Mylar film at a load of 1.0 mg / cm². The results for sheet resistance (Ω / square) are summarized in Table 4a, and the error is based on the standard deviation of three measurements.

[0259]

[0260]

[0261] Table 4a - Summary of 4-point probe resistivity measurement results for samples E1 to E14.

[0262] DCIR (DC Internal Resistance) and the generated ASI (Area Specific Impedance) are key factors in measuring the internal resistance of a lithium-ion battery electrode. In a typical measurement, a pre-formed battery can be cycled for 3 cycles at C / 2. With the electrode delithiated, a C / 2 discharge current is applied for 1 hour to achieve ~50% lithiation. The battery is rested for 30 minutes to equilibrate at OCV (Open Circuit Voltage), then a 5C current pulse is applied for 10 seconds, followed by a 30-minute rest to reach OCV. During the 10-second pulse, the voltage response is sampled at a higher frequency to accurately determine the average internal resistance. The resistance is then calculated from V = IR using the difference between the OCV (the linear average between the initial OCV before the pulse and the subsequent OCV) and the measured voltage. The ASI is then generated by multiplying the resistance by the electrode area.

[0263] The results of this test are presented in Table 5 below.

[0264]

[0265]

[0266] Table 5 - Summary of DCIR / ASI measurement results for samples 1, 2, 4, 7, 14, 16, and 17.

[0267] For multiple samples, reversible specific capacity C / 20, initial Coulomb efficiency, Li / Li+ at nominal lithiation voltage versus C / 20, 5C / 0.5C capacity retention, and 10C / 0.5C capacity retention were also tested, and the results are shown in Table 6 below. Nominal lithiation voltage versus Li / Li+ was calculated by dividing the integral of the V / Q curve by the total capacity of the second cycle C / 20 lithiation. Capacity retention at 10C and 5C was calculated by dividing the specific capacity at 10C or 5C by the specific capacity at 0.5C. It should be noted that capacity retention was tested using symmetric cycling tests with equivalent C-rates for lithiation and delithiation. When tested with an asymmetric cycling program, 10C / 0.5C capacity retention greater than 89% is routinely observed.

[0268] Samples E1-E10 were tested with slight differences as shown in Table 6a, the reversible capacity shown is the second cycle delithiation capacity at C / 10, the nominal lithiation voltage versus Li / Li+ is at C / 10 in the second cycle, and the rate test was performed with an asymmetric cycling program without a constant voltage step (i.e., constant current), with lithiation at C / 5 and delithiation at increasing C-rates.

[0269]

[0270]

[0271] Table 6 - Summary of electrochemical test results of Li-ion half-coin cells using multiple samples. In general (though not exclusively), it is advantageous to have higher capacity, higher ICE, lower nominal voltage, and higher capacity retention.

[0272]

[0273] Table 6a - Summary of electrochemical test results of Li-ion half-coin cells using multiple samples.

[0274] Variations of mixed niobium oxide-based Wadsley-Roth and Bronze structures as presented in the claims demonstrate the applicability of the present invention to improve active material performance in Li-ion batteries. By replacing non-Nb cations to form mixed cation structures as described, entropy (cf. disorder) can be increased in the crystal structure, and the potential energy barrier for Li-ion diffusion can be reduced through the introduction of minor defects (e.g., Sample E7, 16). Variations by creating mixed cation structures that maintain the same overall oxidation state represent potential improvements by altering the ionic radius, e.g., Mo in Sample 14 6+ Cations W 6+ Replace with or Al in samples E4 and E5 3+ About Fe 3+ or Ga 3+ By replacing it, it is possible to induce minor changes in crystal parameters and lithium-ion cavities (e.g., tuning the reversibility of Type VI cavities in Wadsley-Roth structures) that can improve capacity, Li-ion diffusion, and reduce Li-ion trapping to increase Coulomb efficiency of cycling. This can be achieved through modifications caused by creating a mixed cation structure that results in an increased oxidation state (e.g., Zn in sample E2). 2+ Ge to replace 4+ or Zr in sample 19 4+ About Mo 6+ ) is compounded by introducing additional electron-holes into the structure to aid electrical conductivity and exhibits similar potential benefits due to altered ionic radii related to capacity and efficiency. Modification by creating a mixed cation structure that reduces oxidation state (e.g., Ge in sample E7) 4+ To replace K + and Co 3+ , in Sample 2 Mo 6+ To replace Ti 4+Compounded by introducing oxygen vacancies and additional electrons within the structure to aid electrical conductivity, exhibiting similar potential benefits associated with altered ionic radii related to capacity and efficiency. Modifications induced by oxygen deprivation during high-temperature processing under inert or reducing conditions demonstrate a small proportion of oxygen loss in the structure, providing reduced structures with significantly improved electrical conductivity (e.g., Samples 5, E10 and E12-14) and improved electrochemical properties, such as capacity retention at high C-velocities (e.g., Sample 5, E13). The combination of mixed cationic structures and induced oxygen deprivation allows for compounding with several beneficial effects (e.g., increased capacity, reduced electrical resistance) (e.g., Sample 18, E8).

[0275] Figures 12, 13, and 19 show undeformed and deformed MoNb in the first two forming cycles at a rate of C / 20. 12 O 33 (Fig. 12 - Samples 1 and 6) ZrNb 24 O 62 (Fig. 13 - Samples 6 and 7) and W7Nb4O 31 Figure 19 shows representative lithiation / delithiation curves for samples 12 and 13. In Figure 12, approximately 90% of the capacity for the demonstrated sample 16 is cathode ( ca. It is shown to be in a narrow voltage range of 1.2 to 2.0 V, and about 90% of the capacitance for Sample 7 demonstrated in Fig. 13 is cathode ( ca. ) It is shown to be within a narrow range of 1.25 to 1.75 V; this data highlights the attractive voltage profile achievable with MNO crystals based on Wadsley-Roth crystal structures. In Fig. 19, approximately 90% of the capacity for sample 13 is cathode ( ca.It was found to be in a narrow range of 1.2 to 2.2 V; this demonstrates that an attractive voltage profile is achieved with MNO crystals based on a tetragonal bronze crystal structure. Second, composite metal oxide samples 7, 16, and 13 demonstrate improved capacity compared to the undeformed crystal samples 1, 6, and 12. This is attributed to the cations contained in the composite structure, as the capacity increases due to an increase in the number of sites within the crystal where Li ions can be accommodated, resulting from different ionic radii and oxidation states. An increase in ICE was observed between samples 1 and 16 and samples 12 and 13, further demonstrating that Li ions inserted into the deformed crystal structure can be more efficiently delithiated as the Li ion sites are altered, enabling their de-intercalation.

[0276] Figure 24 demonstrates the particle size distribution of samples E2, E4, E8, and E11, which mainly contain a single peak with a narrow distribution, i.e., D 10 and D 90 is D 50 The values ​​are similar. This is advantageous for processing materials in the electrode slurry for efficient packing and maintaining homogeneous electrochemical performance (for example, smaller particles are fully lithiated before larger particles due to shorter diffusion distances).

[0277] Fig. 25 shows Zn in particular 2+ Cations of Ge with a higher valence 4+ It illustrates the benefits of modifying sample E1 in relation to improving the observed specific capacity by replacing with cations. Fig. 26 shows Ge 4+Figure 28 shows the improved specific capacity observed when modifying sample E6 by replacing it with K and Co cations, i.e., cations with reduced valence. Figure 28 demonstrates the improvement in ICE and the reduction in nominal lithiation voltage made possible by improving the reversibility of the lithiation / delithiation process and by introducing induced oxygen vacancies that reduce polarization effects through improved conductivity.

[0278] In all tested materials, each material according to the present invention was found to be improved compared to the undeformed 'base' crystal structure. This is inferred from resistivity / impedance measurements by two different methods and electrochemical tests performed on lithium-ion half-coin cells, particularly capacity retention at increased current densities (see rates, Table 6, Figures 14 and 15). Without wishing to be bound by theory, the inventors propose that this is the result of increased ionic and electronic conductivity of the material following defect introduction, or a change in the crystal lattice due to a change in ionic radius; this is also evidenced by DCIR / ASI (Table 5) and EIS (Figure 16) measurements showing reduced resistance or impedance upon material modification. Compared to the undeformed 'base' material, the Li-ion diffusion rate in the material according to the present invention is also likely to increase. Since doping / exchange with metal ions of different sizes can expand or contract the crystal lattice and allow for more insertion of Li-ions or more reversibility of insertion as much as possible in the undeformed structure, the specific capacity itself can also increase in some cases, as shown in Table 6.

[0279] The data in Table 4 show a significant decrease in resistivity between Sample 1 (comparison) and Samples 2, 4, 5, 14, 15, 16, 18, and 22, which demonstrates the effect of the embodiments of the present invention in improving the electrical conductivity of the crystal structure through both cation exchange, oxygen depletion, and carbon coating. Samples 17, 19, and 20 also exhibit similarly low resistivity compared to Sample 6. Although the resistivity increased slightly upon the introduction of 0.05 equivalents of V species into the base crystal of Sample 7, an improvement in capacity was observed due to changes in available lithium ion sites in the crystal lattice, which are possible as a result of the different ionic radii of V relative to Zr (see Table 6).

[0280] The data in Table 5 reflects the trends shown in Table 4, exhibiting a significant decrease in DCIR / ASI from Sample 1 (Comparison) to Samples 2, 4, 14, 16, 18, and 22. Samples 7, 17, and 19 exhibit higher DCIRs compared to these, but this is associated with different base crystal structures. Without wishing to be bound by theory, the inventors suggest that due to changes in the crystal lattice caused by introduced cations with different ionic radii, Samples 7, 17, and 19 are the comparison material (ZrNb) of Sample 6. 24 O 62 It is assumed that it represents an increase in DCIR / ASI compared to ). However, as shown in Table 4, the electrical resistivity decreases, thereby minimizing Joule heating and enabling a more uniform current distribution throughout the material, which in turn can improve the safety and lifetime of the Li-ion system; thus, this is still advantageous for the conductive mode of this structure for samples 17 and 19. In the case of sample 7, there is no proven improvement using V to exchange for Zr, but as discussed above, the capacity increases.

[0281] In Table 6, across most samples, there is a trend toward improved capacity, initial Coulomb efficiency (ICE), nominal lithiation voltage versus Li / Li+, and, importantly, capacity retention at 5C and 10C versus 0.5C for the material according to the present invention versus the comparative 'base' material (e.g., samples 1, 6, 8, 10, 12). For example, samples 2, 3, 4, 5, 14, 15, 16, 18, and 22 all show improvements in one or more of these parameters compared to sample 1. This is also the case for samples 7, 17, and 19 versus sample 6 for several parameters; samples 11 and 21 versus 10 for which improvements in capacity or capacity retention were observed; sample 9 versus 8 for which improvements in ICE and capacity retention were observed; and sample 13 versus 12* for which improvements in all parameters were observed.

[0282] Figures 14 and 15 demonstrate improved capacity retention of the material according to the present invention (samples 4, 16, 7, 17) at higher cycling rates compared to the comparative material (samples 1 and 6).

[0283] Electrochemical Impedance Spectroscopy (EIS) measurements were also performed to gain a further understanding of the impedance present at the electrodes of Li-ion batteries. In a typical measurement, the battery is prepared to ~50% lithiation for DCIR measurements, and then the frequency of the AC charge / discharge current pulses is changed while measuring the impedance. By plotting the real and imaginary components on the axes and changing the AC frequency, a Nyquist plot is generated. In this plot for Li-ion batteries, various types of impedance of the battery can be identified, but they are generally complex to interpret. For example, ohmic resistance can be partially separated from electrochemical double layer effects and also separated from diffusion effects.

[0284] Figures 16(a) and (b) show the EIS spectra for (comparative) sample 1 and samples 16 and 7 (samples according to the present invention).

[0285] ***

[0286] Features disclosed in the foregoing description, or in the claims below, or in the accompanying drawings, expressed in a specific form or in an embodiment of a means for performing a disclosed function or a method or process for obtaining a disclosed result, may be used to realize the present invention in various forms, individually or in any combination of such features, where appropriate.

[0287] Although the present invention has been described in relation to the exemplary embodiments described above, many equivalent modifications and variations will be apparent to those skilled in the art at the time of this disclosure. Accordingly, the exemplary embodiments of the present invention described above are considered exemplary and not restrictive. Various modifications to the described embodiments may be made without departing from the spirit and scope of the present invention.

[0288] To eliminate any doubt, all theoretical descriptions provided herein are for the purpose of enhancing the reader's understanding. The inventors do not intend to be bound by such theoretical descriptions.

[0289] All section titles used in this specification are for organizational purposes only and should not be interpreted as limiting the subject matter of the invention described.

[0290] Throughout this specification, including the claims below, unless otherwise required by the context, the words “comprise” and “include,” and variations such as “comprises,” “comprising,” and “including,” will be understood to mean that they include a specified integer or step or group of integers or steps, but do not exclude any other integer or step or group of integers or steps.

[0291] It should be noted that, as used in the specification and appended claims, the singular forms (“a,” “an,” and “the”) include plural references unless the context clearly indicates otherwise. Ranges may be indicated herein by “about” one specific value and / or “about” another specific value. When such ranges are indicated, other embodiments include one specific value and / or another specific value. Similarly, when values ​​are indicated as approximations, it will be understood by the use of the antecedent “about” that the specific value constitutes another embodiment. The term “about” in relation to a number is optional and means, for example, + / - 10%.

[0292] Numbered embodiments

[0293] The numbered embodiments below form part of the description.

[0294] 1. General formula [M1] x [M2] (1-x) [Nb] y [O] z Active electrode material represented by: in the above general formula,

[0295] M1 and M2 are different;

[0296] M1 represents one or more of Ti, Mg, V, Cr, W, Zr, Nb, Mo, Cu, Fe, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Te, Se, Si, Sb, Y, La, Hf, Ta, Re, Zn, In, or Cd;

[0297] M2 represents one or more of Mg, V, Cr, W, Zr, Nb, Mo, Cu, Fe, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Te, Se, Si, Sb, Y, La, Hf, Ta, Re, Zn, In, or Cd; where

[0298] x satisfies 0 < x < 0.5;

[0299] y satisfies 0.5 ≤ y ≤ 49 and

[0300] z satisfies 4 ≤ z ≤ 124.

[0301] 2. In Embodiment 1,

[0302] An active electrode material in which M2 is selected from one or more of Mo, W, V, or Zr.

[0303] 3. In Embodiment 2,

[0304] The above [M1] x [M2] (1-x) [Nb] y [O] z A, an active electrode material selected from the group consisting of the following:

[0305] M1 x Mo (1-x) Nb 12 O (33-33α)

[0306] M1 x W (1-x) Nb 12 O (33-33α)

[0307] M1 x V (1-x) Nb9O (25-25α)

[0308] M1 x Zr (1-x) Nb 24 O (62-62α)

[0309] M1 x W (1-x) Nb 0.57 O (4.43-4.43α)

[0310] M1 x W (1-x) Nb 0.89 O (5.22-5.22α),

[0311] Here, M1 represents one or more of Ti, Mg, V, Cr, W, Zr, Nb, Mo, Cu, Fe, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Te, Se, Si, Sb, Y, La, Hf, Ta, Re, Zn, In, or Cd; where

[0312] x satisfies 0 < x < 0.5;

[0313] α is 0 ≤ α ≤ 0.05 is satisfied.

[0314] 4. In any one of embodiments 1 to 3,

[0315] The above active electrode material is an active electrode material that is oxygen-deficient.

[0316] 5. General formula [M] x [Nb] y [O] (z'-z'α) An active electrode material represented by and selected from the group consisting of:

[0317] MoNb 12 O (33-33α)

[0318] WNb 12 O (33-33α)

[0319] VNb9O (25-25α)

[0320] ZrNb 24 O (62-62α)

[0321] W7Nb4O (31-31α)

[0322] W9Nb8O (47-47α),

[0323] Here, α is 0 < α ≤ 0.05 is satisfied.

[0324] 6. In any one of embodiments 1 to 5,

[0325] An active electrode material having at least a portion of the above material having a Wadsley-Roth crystal structure and / or a tetragonal tungsten bronze crystal structure.

[0326] 7. In any one of embodiments 1 to 6,

[0327] An active electrode material comprising a plurality of primary crystal grains, wherein some or all of the primary crystal grains are selectively aggregated into secondary particles.

[0328] 8. In embodiment 7,

[0329] An active electrode material having an average diameter of the primary crystal grains of 10 nm to 10 μm.

[0330] 9. In embodiment 7 or embodiment 8,

[0331] An active electrode material in which part or all of the primary crystal grains are aggregated into secondary particles, and the average diameter of the secondary particles is 1 μm to 30 μm.

[0332] 10. In any one of embodiments 1 to 9,

[0333] An active electrode material comprising a carbon coating formed on the surface of the primary crystal grains and / or secondary particles.

[0334] 11. In embodiment 10,

[0335] An active electrode material in which the carbon coating is present in an amount of up to 5 w / w% based on the total weight of the active electrode material.

[0336] 12. In any one of embodiments 1 to 11,

[0337] Active electrode material, wherein the crystal structure of the active electrode material determined by X-ray diffraction analysis corresponds to one or more of the following crystal structures:

[0338] MoNb 12 O 33

[0339] WNb 12 O 33

[0340] ZrNb 24 O 62

[0341] VNb9O 25

[0342] W7Nb4O 31

[0343] W9Nb8O 47 .

[0344] 13. In any one of embodiments 1 to 12,

[0345] Active electrode material further comprising Li and / or Na.

[0346] 14. An electrochemical device comprising an anode, a cathode, and an electrolyte disposed between the anode and the cathode, wherein the anode comprises an electrode active material according to any one of embodiments 1 to 13.

[0347] 15. Use of an electrode active material according to any one of embodiments 1 to 13 as an anode active material or a component of an anode active material in the anode together with a cathode and an electrolyte in (i) a lithium-ion battery for charging and discharging; or (ii) a sodium-ion battery for charging and discharging.

[0348] 16. A method for treating an electrode active material according to any one of embodiments 1 to 13 as an anode active material or within an anode active material,

[0349] (i) in the case of a lithium-ion battery, the method comprises the step of diffusing lithium ions into the anode active material; or (ii) in the case of a sodium-ion battery, the method comprises the step of diffusing sodium ions into the anode active material.

[0350] 17. A method for manufacturing an active electrode material according to any one of embodiments 1 to 13, wherein the method comprises:

[0351] A step of providing one or more precursor materials;

[0352] A step of mixing the above precursor materials to form a precursor material mixture; and

[0353] A step of forming an active electrode material by heat-treating a precursor material mixture in a temperature range of 400℃ to 1350℃.

[0354] A method including

[0355] 18. In embodiment 17,

[0356] A method for manufacturing an active electrode material, wherein one or more of the above precursor materials comprise a source of Mo, W, Zr, or V, and a source of Nb.

[0357] 19. In embodiment 17 or embodiment 18

[0358] A method for manufacturing an active electrode material, wherein one or more of the above precursor materials comprise an M1 ion source, an M2 ion source, and an Nb source, and the produced active electrode material is a material such as that defined in any one of Examples 1 to 4, or Examples 6 to 13 depending on Example 1.

[0359] 20. In embodiment 17,

[0360] A method for manufacturing an active electrode material, wherein the above-mentioned precursor material comprises one or more metal oxides, metal hydroxides, metal salts, or oxalates.

[0361] 21. In any one of embodiments 17 to 20,

[0362] A method in which one or more of the above precursor materials are granular materials and optionally have an average particle size with a diameter of < 20 μm.

[0363] 22. In any one of embodiments 17 to 21,

[0364] A method wherein the step of mixing the above precursor materials to form a precursor material mixture is performed by a method selected from dry or wet planetary ball milling, rolling ball milling, high-shear milling, air jet milling, and / or impact milling.

[0365] 23. In any one of embodiments 17 to 22,

[0366] A method in which the step of heat-treating the above precursor material mixture is performed for a period of 1 to 14 hours.

[0367] 24. In any one of embodiments 17 to 23,

[0368] A method wherein the step of heat-treating the above precursor material mixture is performed in a gaseous atmosphere, and the gas is selected from air, N2, Ar, He, CO2, CO, O2, H2, and mixtures thereof.

[0369] 25. In any one of embodiments 17 to 24,

[0370] The above method,

[0371] (i) a step of heat-treating the active electrode material;

[0372] (ii) mixing the active electrode material with a carbon source and optionally further heating the mixture to form a carbon coating on the active electrode material;

[0373] (iii) a step of spray-drying the active electrode material; and / or

[0374] (iv) A step of changing the particle size of the active electrode material by milling the active electrode material.

[0375] A method comprising one or more post-processing steps selected from.

[0376] References

[0377] To more fully describe and disclose the present invention and the state of the art to which the present invention pertains, numerous publications are cited above. Full citations of these references are provided below. The full text of each of these references is incorporated herein.

[0378] Goodenough and Park, “The Li-Ion Rechargeable Battery: A Perspective”, Journal of the American Chemical Society 2013 135 (4), 1167-1176, DOI: 10.1021 / ja3091438

[0379] Griffith et al., “High-Rate Intercalation without Nanostructuring in Metastable Nb2O5Bronze Phases, Journal of the American Chemical Society 2016 138 (28), 8888-8899, DOI: 10.1021 / jacs.6b04345

[0380] Griffith et al., "Structural Stability from Crystallographic Shear in TiO2Nb2O5Phases: Cation Ordering and Lithiation Behavior of TiNb 24 O 62 Inorganic Chemistry (2017), 56, 7, 4002-4010

[0381] Montemayor et al., "Lithium insertion in two tetragonal tungsten bronze type phases, M8W9O47 (M = Nb and Ta)", Journal of Material Chemistry (1998), 8, 2777-2781

[0382] Zhou et al., "Facile Spray Drying Route for the Three-Dimensional Graphene Encapsulated Fe2O3Nanoparticles for Lithium Ion Battery Anodes", Ind. Eng. Chem. Res. (2013), 52, 1197-1204

[0383] Zhu et al., "MoNb 12 O 33 as a new anode material for high- capacity, safe, rapid and durable Li + storage: structural characteristics, electrochemical properties and working mechanisms", J. Mater. Chem. A. (2019), 7 , 6522-6532

[0384] Yang et al., "Porous ZrNb 24 O 62Nanowires with Pseudocapacitive Behavior Achieve High-Performance Lithium-Ion Storage J. Mater. Chem. A. (2017) 5. 10.1039 / C7TA07347J.

Claims

Claim 1 General formula [M1] x [M2] (1-x) [Nb] y [O] z An active electrode material represented by: wherein, in the above general formula, M1 and M2 are different; M1 represents one or more of Ti, Mg, V, Cr, W, Zr, Mo, Cu, Fe, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Te, Se, Si, Sb, Y, La, Hf, Ta, Re, Zn, In, or Cd; M2 represents one or more of V, Cr, W, Zr, Mo, Ga, Ge, Al, or Zn; x satisfies 0 < x < 0.5; y satisfies 0.5 ≤ y ≤ 49; and z satisfies 4 ≤ z ≤ 124, and at least a portion of the material has a Wadsley-Roth crystal structure and / or a tetragonal tungsten bronze crystal structure. Claim 2 An active electrode material according to claim 1, wherein M2 is selected from one or more of Mo, W, V, or Zr. Claim 3 In paragraph 1, the above [M1] x [M2] (1-x) [Nb] y [O] z A. Active electrode material selected from the group consisting of the following: (i) M1 x Mo (1-x) Nb 12 O (33-33α) M1 x W (1-x) Nb 12 O (33-33α) M1 x V (1-x) Nb9O (25-25α) M1 x Zr (1-x) Nb 24 O (62-62α) M1 x W (1-x) Nb 0.57 O (4.43-4.43α) M1 x W (1-x) Nb 0.89 O (5.22-5.22α) M1 x Zn (1-x) Nb 17 O (43.5-43.5α) M1 x Al (1-x) Nb 11 O (29-29α) M1 x Ga (1-x) Nb 11 O (29-29α) M1 x Ge (1-x) Nb 18 O (47-47α) M1 x W (1-x) Nb -1.125 O (5.81-5.81α) M1 x W (1-x) Nb -3.2 O (11-11α) M1 x Al (1-x) Nb 49 O (124-124α) M1 x Ga (1-x) Nb 49 O (124-124α) ; or(ii) M1 x Mo (1-x) Nb 12 O (33-33α) M1 x W (1-x) Nb 12 O (33-33α) M1 x V (1-x) Nb9O (25-25α) M1 x Zr (1-x) Nb 24 O (62-62α) M1 x W (1-x) Nb 0.57 O (4.43-4.43α) M1 x W (1-x) Nb 0.89 O (5.22-5.22α) M1 x Zn (1-x) Nb 17 O (43.5-43.5α) M1 x Al (1-x) Nb 11 O (29-29α) M1 x Ge (1-x) Nb 18 O (47-47α) ; or(iii) M1 x Mo (1-x) Nb 12 O (33-33α) M1 x W (1-x) Nb 12 O (33-33α) M1 x V (1-x) Nb9O (25-25α) M1 x Zr (1-x) Nb 24 O (62-62α) M1 x W (1-x) Nb 0.57 O (4.43-4.43α) M1 x W (1-x) Nb 0.89 O (5.22-5.22α) ; Here, M1 represents one or more of Ti, Mg, V, Cr, W, Zr, Mo, Cu, Fe, Ga, Ge, Ca, K, Ni, Co, Al, Sn, Mn, Ce, Te, Se, Si, Sb, Y, La, Hf, Ta, Re, Zn, In, or Cd; where x satisfies 0 < x < 0.5; and α satisfies 0 ≤ α ≤ 0.

05. Claim 4 In claim 1, the active electrode material is formula M1 x Mo (1-x) Nb 12 O (33-33α) An active electrode material having, where α satisfies 0 ≤ α ≤ 0.

05. Claim 5 In claim 1, the active electrode material is formula M1 x W (1-x) Nb 0.57 O (4.43-4.43α) An active electrode material having, where α satisfies 0 ≤ α ≤ 0.

05. Claim 6 In claim 1, the active electrode material is formula M1 x Zn (1-x) Nb 17 O (43.5-43.5α) An active electrode material having, where α satisfies 0 ≤ α ≤ 0.

05. Claim 7 In claim 1, the active electrode material is formula M1 x Al (1-x) Nb 11 O (29-29α) An active electrode material having, where α satisfies 0 ≤ α ≤ 0.

05. Claim 8 An active electrode material according to claim 1, wherein (i) M1 represents one or more of K, Mg, Ca, Y, Ti, Zr, Hf, V, Ta, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, Si, Ge, Sn, Sb; or (ii) M1 represents one or more of Ti, Mg, V, Cr, W, Zr, Mo, Cu, Ga, Ge, K, Ni, Al, Hf, Ta, or Zn; or (iii) M1 represents one or more of Ti, Mg, V, Cr, W, Zr, Mo, Ga, Ge, Al, or Zn. Claim 9 An active electrode material according to claim 1, wherein M1 has an oxidation state equal to or lower than M2, and optionally M1 has an oxidation state lower than M2. Claim 10 An active electrode material according to claim 1, wherein M1 comprises at least one cation having a 4+ oxidation state and M2 comprises at least one cation having a 6+ oxidation state; optionally, M1 has a 4+ oxidation state and M2 has a 6+ oxidation state. Claim 11 In claim 1, the crystal structure of the active electrode material determined by X-ray diffraction corresponds to the crystal structure of the active electrode material in an undeformed form, and the undeformed form is given by the formula [M2][Nb] y [O] z It is represented as, where M2 consists of a single element, the above-mentioned undeformed form is not oxygen-deficient, and the above-mentioned undeformed form is M2 I Nb5O 13 , M2 I 6Nb 10.8 O 30 , M2 II Nb2O6, M2 II 2Nb 34 O 87 , M2 III Nb 11 O 29 , M2 III Nb 49 O 124 , M2 IV Nb 24 O 62 , M2 IV Nb2O7, M2 IV 2Nb 10 O 29 , M2 IV 2Nb 14 O 39 , M2 IV Nb 14 O 37 , M2 IV Nb6O 17 , M2 IV Nb 18 O 47 , M2 V Nb9O 25 , M2 V 4Nb 18 O 55 , M2 V 3Nb 17 O 50 , M2 VI Nb 12 O 33 , M2 VI 4Nb 26 O 77 , M2 VI 3Nb 14 O 44 , M2 VI 5Nb 16 O 55 , M2 VI 8Nb 18 O 69 , M2 VI Nb2O8, M2 VI 16 Nb 18 O 93 , M2 VI 20 Nb 22 O 115 , M2 VI 9Nb8O 47 , M2 VI 82 Nb 54 O 381 , M2 VI 31 Nb 20 O 143 , M2 VI 7Nb4O 31 , M2 VI 15 Nb2O 50 , M2 VI 3Nb2O 14 , and M2 VI 11 Nb 12 O 63 An active electrode material selected from, where numbers I, II, III, IV, V, and VI represent the oxidation states of M2. Claim 12 An active electrode material according to claim 1, wherein (i) x satisfies 0.01 ≤ x ≤ 0.4; and / or (ii) x satisfies 0.05 ≤ x ≤ 0.25; and / or (iii) x is 0.

05. Claim 13 The active electrode material of claim 1, wherein the active electrode material is oxygen-deficient, optionally z is defined as z=(z'-z'α), where α satisfies 0 < α ≤ 0.

05. Claim 14 An active electrode material according to claim 1, wherein substantially all active electrode material has a Wadsley-Roth crystal structure and / or a tetragonal tungsten bronze crystal structure. Claim 15 An active electrode material according to claim 1, wherein the active electrode material comprises a plurality of primary crystal grains, and some or all of the primary crystal grains are selectively aggregated into secondary particles. Claim 16 An active electrode material according to claim 15, wherein the average diameter of the primary crystal grains is 10 nm to 10 μm. Claim 17 An active electrode material according to claim 15, wherein part or all of the primary crystal grains are aggregated into secondary particles, and the average diameter of the secondary particles is 1 μm to 30 μm or 2 μm to 15 μm. Claim 18 The active electrode material according to claim 1, wherein the active electrode material has a BET surface area in the range of 0.1-100 m² / g, or 0.5-50 m² / g, or 1-20 m² / g. Claim 19 An active electrode material according to claim 1, wherein the active electrode material comprises a carbon coating formed on the surface of primary crystal grains and / or secondary particles. Claim 20 In claim 19, the active electrode material, wherein the carbon coating is present in an amount of 5 w / w% or less based on the total weight of the active electrode material. Claim 21 In claim 1, the active electrode material, wherein the crystal structure of the active electrode material determined by X-ray diffraction analysis corresponds to one or more of the following crystal structures: (i) MoNb 12 O 33 WNb 12 O 33 VNb9O 25 ZrNb 24 O 62 W7Nb4O 31 W9Nb8O 47 Zn2Nb 34 O 87 AlNb 11 O 29 GaNb 11 O 29 GeNb 18 O 47 W 16 Nb 18 O 93 W5Nb -16 O 55 AlNb 49 O 124 GaNb 49 O 124 ; or(ii) MoNb 12 O 33 WNb 12 O 33 VNb9O 25 ZrNb 24 O 62 W4Nb7O 31 W9Nb8O 47 Zn2Nb 34 O 87 AlNb 11 O 29 GeNb 18 O 47 ; or(iii) MoNb 12 O 33 WNb 12 O 33 ZrNb 24 O 62 VNb9O 25 W7Nb4O 31 W9Nb8O 47 . Claim 22 An active electrode material according to claim 1, wherein the crystal structure of the active electrode material does not correspond to the crystal structure of TiNb2O7. Claim 23 An active electrode material according to claim 1, further comprising Li and / or Na. Claim 24 An electrochemical device comprising an anode, a cathode, and an electrolyte disposed between the anode and the cathode, wherein the anode comprises an electrode active material according to any one of claims 1 to 23. Claim 25 A method for manufacturing an active electrode material according to any one of claims 1 to 23, the method comprising: providing one or more precursor materials; mixing the precursor materials to form a precursor material mixture; and heat-treating the precursor material mixture at a temperature range of 400°C to 1350°C to form an active electrode material. Claim 26 delete Claim 27 delete Claim 28 delete Claim 29 delete Claim 30 delete Claim 31 delete Claim 32 delete Claim 33 delete Claim 34 delete

Citation Information

Patent Citations

  • Active material, nonaqueous electrolyte battery, and battery pack

    CN104282899A

  • Active substance, nonaqueous electrolyte battery, and battery pack

    CN104466150A

  • Lithium ion battery anode material and non-aqueous electrolyte battery

    CN109360978A

  • Active material for batteries, nonaqueous electrolyte battery and battery pack

    JP2016177972A